GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2019)
A dataset containing 181938182 species occurrences available in GBIF matching the query: BasisOfRecord: Specimen or Fossil or Unknown evidence. The dataset includes 181938182 records from 10580 constituent datasets: 39 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 289508 records from Canadian Museum of Nature Herbarium. 409 records from A taxonomic monograph of the assassin bug genus Zelus Fabricius (Hemiptera: Reduviidae): 71 species based on 10,000 specimens. 581 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 964 records from Banco de Germoplasma del Real Jardín Botánico Juan Carlos I. 3 records from A new species of Dolichopoda (Orthoptera: Rhaphidophoridae; Dolichopodainae) from Western Greece. 45811 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 446 records from CNIN/Tipos Lepidoptera. 1971 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 314 records from Tejidos colectados en la ventana de biodiversidad del Complejo Cenagoso de Zapatosa, Municipio de Chimichagua, Cesar, Colombia.. 13 records from New Species and Records of Costa Rican Featherwing Beetles (Coleoptera: Ptiliidae). 1 records from Araboplia lorisi new genus and species of Rutelinae from Saudi Arabia (Coleoptera, Scarabaeidae), with comments on the subtribe Popilliina. 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 2780 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 25 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 49232 records from Naturalis Biodiversity Center (NL) - Amphibia and Reptilia. 878 records from COA Bird Collection (Arctos). 120813 records from New Zealand Arthropod Collection (NZAC). 5 records from First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species. 1 records from Cetopirus complanatus (Cirripedia: Coronulidae) from the late Middle Pleistocene human settlement of Pinnacle Point 13 B (Mossel Bay, South Africa). 18 records from Three new species of Miroculis from the Serra da Mocidade National Park, Roraima State, Brazil, with new records and checklist of the Leptophlebiidae (Ephemeroptera). 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 10654 records from Bryophyte specimens of The Nagoya University Museum. 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 34518 records from University of Guam Insect Collection. 22857 records from National Botanic Garden Belgium - Myxomycetes. 10 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 3 records from Morphological and molecular characterization of three Helicotylenchus species from Iran. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 10 records from Revision of the shore-fly genus Peltopsilopa Hendel (Diptera: Ephydridae). 913 records from Distribution of planktic foraminifera of sediment core GIK18287-3. 1 records from Waldsee. 8 records from Lluciapomaresius nisae, a new species of Ephippigerini (Orthoptera: Tettigoniidae: Bradyporinae) from the northeast of the Iberian Peninsula. 3072 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche. 2505 records from ZUEC-ORT - Coleção de Orthoptera do Museu de Zoologia da UNICAMP. 10 records from Redescription of four species of Cytaea Keyserling, 1882 (Araneae: Salticidae). 1189 records from UWIZM Molluscs. 2 records from New species of Simothraulopsis Demoulin, 1966 (Ephemeroptera: Leptophlebiidae) from Northeastern Region of Brazil. 5 records from Additions to the leafhopper subgenus Pediopsoides (Pediopsoides) Matsumura, 1912 (Hemiptera: Cicadellidae: Macropsinae) from Southern China. 6 records from An updated and detailed taxonomical account of the large Branchiopoda (Crustacea: Branchiopoda: Anostraca, Notostraca, Spinicaudata) from the Yale North India Expedition deposited in the Yale Peabody Natural History Museum. 7 records from The inaequalis species-group (Hymenoptera, Chrysididae, Chrysis) in China, with description of a new species. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 382 records from orthopteracollections-nhmj-ioj. 824 records from Bird specimens of Saitama Museum of Natural History. 9605 records from Aves Tanzanian collection at the Natural History Museum of Denmark (SNM). 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 9 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 413 records from (Fig. 5) Sea-surface temperature reconstructions of sediment core MD99-2304. 24370 records from Muséum d'Avignon. 626 records from Mycology collection, Norwegian Forest and Landscape Institute. 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 20 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 4 records from A third species in the rare Australian ant genus Peronomyrmex Viehmeyer (Hymenoptera: Formicidae).. 4 records from A new species of Voria Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica. 9500 records from Plant specimens of Tama City Cultural Foundation. 7 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 5 records from Neoclita pringlei (Scarabaeidae, Cetoniinae), a new relict genus and species from the Drakensberg Range of South Africa. 13 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 55 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 42 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 1 records from Erysipelothrix inopinata sp. nov., isolated in the course of sterile filtration of vegetable peptone broth, and description of Erysipelotrichaceae fam. nov.. 95 records from Poliquetos (Annelida: Polychaeta) del Pacífico Mexicano. 7 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 1904 records from Escarabajos coprófagos de la cuenca alta y media del río Bita, Vichada (Colombia). 173 records from UWIZM Anoles. 589 records from (Appendix 2) DSDP Site 94-610 ostracode species census data. 10 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 1 records from Nothrus pulverulentus. 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 2451 records from Macrobenthos Chukchi Sea, 1986. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 7 records from On the taxonomy and morphology of Leuthneria ruficincta (Lepidoptera: Sesiidae). 7 records from Tobrilus methanus sp. n. and Tripyla posolskii sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 55 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 425 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 48 records from Tardigrad collection of the National Museum of Nature and Science. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 8 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 7 records from Speolabeo, a new genus name for the cave fish Bangana musaei (Teleostei: Cyprinidae). 599 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 20627 records from Herbier Louis-Marie (QFA) - Collection de lichens. 1877 records from Actualización de la Colección de Microorganismos de importancia acuática. 2 records from Morphology and molecules say: Tanytarsus latens, sp. nov. from Finland (Diptera: Chironomidae). 4 records from First record of Limnatis paluda (Hirudinida, Arhynchobdellida, Praobdellidae) from Kazakhstan, with comments on genetic diversity of Limnatis leeches. 16 records from Revisions of two poorly known species of Opisthotropis Günther, 1872 (Squamata: Colubridae: Natricinae) with description of a new species from China. 607514 records from Plant. 3159 records from Grasses of the Forest Herbarium Ibadan (FHI) Nigeria. 4 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 169 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 10 records from The crane fly genus Libnotes Westwood, 1876 (Diptera: Limoniidae) for Korea including two new species and an identification key. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 3 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 1006 records from Colecção Entomológica IIA. 30 records from Equinodermos de las unidades ecológicas someras Expedición Seaflower Serranilla2017 - Proyecto Colombia BIO. 13 records from The first data on species diversity of leeches (Hirudinea) in the Irtysh River Basin, East Kazakhstan. 17155 records from MZFC/Coleccion de Aves. 4567 records from Herbarium WRSL, Main Collection. 2 records from Record of a new species of the genus Viridopromontorius Luna de Carvalho (Strepsiptera: Corioxenidae) from India with a revised key to Corioxenidae. 1 records from Eight species in the Nebela collaris complex: Nebela gimlii (Arcellinida, Hyalospheniidae), a new species described from a Swiss raised bog. 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 6 records from Rango, comportamiento, tamaño de población y conservación de felinos en el Volcán de Colima. 7223 records from Colección Mastozoológica del IADIZA - CCT CONICET Mendoza: IADIZA-CMI. 4551 records from University of Alberta Freshwater Invertebrate Collection (UAFIC). 6943 records from DMNS Egg Collection (Arctos). 17 records from A new genus and species of Haplobainosomatidae (Diplopoda: Chordeumatida) from the MSS of the Sierra de Guadarrama National Park, central Spain. 14923 records from Lepidopterous specimens of Yamagata Prefectural Museum. 7410 records from Helgeland Museum, Lepidoptera. 15590 records from Colección Zoológica de la Universidad del Tolima (CZUT)- Ictiología. 1 records from Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini). 2777 records from Plant (KIWE-PL). 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 221 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 1277 records from Museu Paraense Emílio Goeldi - Chelonia Collection. 1 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 1 records from Orthoptera - SMF. 111710 records from ALCB - Herbário Alexandre Leal Costa. 191799 records from Australian National Insect Collection. 3184 records from Herbarium specimens of Limoges university (LIMO). 10 records from A review of the genus Labeo (Teleostei: Cyprinidae) in Sri Lanka. 4847 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 94857 records from Fish specimens of Kagoshima University Museum. 2 records from Papuaneon, a new genus of jumping spiders from Papua New Guinea (Araneae: Salticidae: Neonini). 44 records from Rivaling the World’s Smallest Reptiles: Discovery of Miniaturized and Microendemic New Species of Leaf Chameleons (Brookesia) from Northern Madagascar. 4185 records from Diptera Collection of Museum and Institute of Zoology PAS. 4059 records from UTEP Invertebrates (Arctos). 356 records from Taxonomic revision of the species of Colletes Latreille, 1802 (Hymenoptera: Colletidae: Colletinae) found in Chile. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 23 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 2 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 1 records from Hesperinus ninae Papp & Krivosheina (Diptera: Hesperinidae) from Georgia: the second record of this peculiar species. 998 records from Korean Ethnobotany Database. 163 records from Relative abundance of coccosphere-units at site GIK23414. 10070 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 481 records from Herbario MAIA, colección Flora Forestal del INIA-CIFOR. 8 records from A new deep-water species of Alpheopsis Coutière, 1897 from the Indo-West Pacific (Decapoda: Alpheidae). 65923 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 41 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 23643 records from CNIN/Abejas de México/Apoidea. 325 records from Diversidad genética del cultivo del chile (Capsicum spp) determinada por isoenzimas y RFLP's tipos: serrano, jalapeño, manzano y silvestres en su área de distribución. 2 records from Scaphisoma poussereaui sp. nov. from La Réunion (Coleoptera: Staphylinidae: Scaphidiinae), arange extension of the S. tricolor species group. 1567 records from Flora útil del Municipio de la Huerta, Jalisco. 1703 records from Slovenian Fungal Database - Boletus informaticus. 1910 records from Chucki_Seaooplankton1953/4. 10 records from Review of the New World genus Nanium Townes, 1967 (Hymenoptera: Ichneumonidae: Ctenopelmatinae), with two new species from the Neotropical region. 215 records from The Diptera Site. 1726 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 12 records from Endogean and cavernicolous Coleoptera of the Balkans. XVII. A new species of the genus Speluncarius Reitter, 1886 (Coleoptera, Carabidae, Harpalinae, Pterostichini) from Croatia. 2 records from Two small species of Cremohipparion (Equidae, Mammalia) from Samos, Greece. 3 records from Two new brackish-water species of Macrostomum (Platyhelminthes, Macrostomida) from mangrove wetland in southern China. 2247 records from NIAES microbial inventory, "microForce" microbe collection, Tsukuba, National Institute for Agro-Environmental Sciences, Japan. 4 records from A new genus of Silvaninae (Coleoptera: Silvanidae) with two new species from the Malay Peninsula. 10354 records from Herpetological collection of National Museum of Nature and Science. 353 records from (Tables T2, T4) Siliceous phytoplankton of ODP Site 175-1077. 6 records from Moema apurinan sp. n. and Aphyolebias boticarioi sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): two new annual killifishes from the Rio Purus basin, Brazilian Amazon.. 302 records from UF Environmental Archaeology Tick Island Zooarchaeological Data. 116446 records from Naturalis Biodiversity Center (NL) - Crustacea. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 12147 records from Danish Ants (Formicidae). 25 records from Brown algae specimens of Komatsu City Museum. 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 273 records from BMHS Herbarium Collection. 1143 records from Calcareous nanofossils in late Pliocene sediments of ODP Site 162-982. 55 records from Fauna íctica del río Arquía, en las estribaciones del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 25098 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 98 records from Distribution of planktonic foraminifera in DSDP Hole 90-594 east of New Zealand. 585 records from Ascomycetes of Russian Fennoscandia. 207 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 241 records from Fishes of the Cusiana River (Meta River basin, Colombia). 3901 records from Colecção Entomológica do Departamento de Sanidade Vegetal - Ministério da Agricultura e Segurança Alimentar. 370 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 1804 records from The Broward College Insect Collection. 2840 records from (Appendix) Dinoflagellate abundance in ODP Site 202-1233. 76 records from Relative abundance of coccosphere-units of sediment core GIK23411-5. 1926 records from Ibaraki Nature Museum, Mammals collection. 23552 records from Berea College, Ralph L. Thompson Herbarium. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 19 records from Pterophoridae (Lepidoptera) fauna of the Republic of Tuva. 11 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 1 records from Description of a new species of Hyalinocerus (Hemiptera: Cicadellidae) from southwestern China, with an update on the generic diagnosis. 5 records from Rediscovery and redescription of a deep-sea shrimp Lebbeus longidactylus (Kobjakova, 1936) (Crustacea: Decapoda: Caridea: Thoridae) based on material from the Nemuro Strait, southwestern Sea of Okhotsk. 30 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 2 records from The second species of Phanoperla (Plecoptera: Perlidae) from China, P. hainana sp. nov., from Hainan Island. 63 records from Polypterus mokelembembe, a new species of bichir from the central Congo River basin (Actinopterygii: Cladistia: Polypteridae).. 139383 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 7 records from Description of two new species of Seinura Fuchs, 1931 (Nematoda: Aphelenchoididae) from Iran. 17 records from Quill mites (Acariformes: Syringophilidae) associated with birds of Mexico. 2 records from The sharpshooter genus Iragua Melichar: a new Colombian species, the female of I. ferruginea Cavichioli, and a key to males of the genus (Insecta: Hemiptera: Cicadellidae: Cicadellini). 5 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 2 records from A new slipper lobster of the genus Petrarctus Holthuis, 2002 (Crustacea, Decapoda, Scyllaridae) from Southwest coast of India. 7 records from Sertania gen. nov., a new genus of butterflies (Lepidoptera: Riodinidae) from the South American dry diagonal. 2 records from New species and records of Scaphobaeocera CSIKI from New Guinea (Coleoptera: Staphylinidae: Scaphidiinae). 6 records from Re-description of two spiny clam shrimps (Crustacea: Branchiopoda: Spinicaudata) of the Indian subcontinent from Daday de Dees's collection at MNHN with new insights on the validity of Eulimnadia compressa (Baird, 1860) and Eulimnadia chaperi (Simon, 1886). 313 records from Genera of the Asian Catfish Families Sisoridae and Erethistidae (Teleostei: Siluriformes).. 121405 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 12 records from Two new species of orb-weaving spiders of the genus Larinia (Araneae, Araneidae) in meridional Brazil. 3918 records from Collembola Collection. 16 records from A new species of the spider genus Wirada (Araneae, Theridiidae) from Mexico, with taxonomic notes on the genus and a key to the species. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 149 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 33454 records from SP-Bryophyta - Maria Eneyda P. Kauffman Fidalgo. 2364 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 83 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 204 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanterriidae).. 4998 records from Ohio State University Tetrapod Division - Amphibian Collection (OSUM). 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 16 records from Revision of the Australian leaf beetle genus Cheiloxena Baly, 1860 (Coleoptera: Chrysomelidae: Spilopyrinae). 29 records from Nomenclatural and type catalogue of Athoracophoridae (Mollusca: Eupulmonata: Succineoidea): a synopsis of the first 185 years of biodiscovery in the South West Pacific region. 28 records from Plant - Plant Virus (KIDR-PL). 1047 records from (Appendix A2) Planktonic foraminifera of ODP Hole 159-958A. 11961 records from MEXU/Leguminosae. 117925 records from KUBI Paleobotany Collection. 117269 records from Coleção Entomológica do Museu Nacional / UFRJ. 2 records from Waldstück Bremerhagen LK Bio Kl. 12. 1 records from A new vertebrate for Europe: the discovery of a range-restricted relict viper in the western Italian Alps. 7 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 33 records from Nothogreniera new genus, for two species of Australian " Paracnephia " (Diptera: Simuliidae). 794914 records from Western Australian Museum provider for OZCAM. 13144 records from El banco de datos del Herbario HCIB en línea (Fase I): Implementación del Sistema Biótica. 3998 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 1 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 424 records from Mamíferos voladores y no voladores del suroccidente colombiano. 18026 records from Colección de Hongos del Herbario de la Universidad de La Laguna: TFC Mic. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 3 records from First records of Edwardsiana sociabilis (Ossiannilsson, 1936) and Laburrus pellax (Horváth, 1903) (Hemiptera, Auchenorrhyncha: Cicadellidae) in Switzerland. 30 records from A checklist of the millipedes (Diplopoda) of Myanmar, with an updated list of Leonardo Fea’s collecting localities. 749 records from (Appendix Table 3) Relative abundances of planktonic foraminiferal species in sediment core MD01-2390. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from A new high-altitude species of centipede from the Andes of Ecuador (Chilopoda, Geophilomorpha, Schendylidae). 1 records from Hymenoptera: Eucoilinae (Cynipoidea). 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 3 records from Two new species of Austrotinodes Schmid (Insecta, Trichoptera, Ecnomidae) from southeastern Brazil. 1513 records from M. Gollop Collection. 37 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 53203 records from Naturalis Biodiversity Center (NL) - Diptera. 4 records from Trachyuropodid mites (Acari: Uropodina) from South-East Asia: catalog, new key and description of two new species. 8 records from Rediscovery of a fossil dolichoderine ant lineage (Hymenoptera: Formicidae: Dolichoderinae) and a description of a new genus from South America.. 2 records from Schulhof Gymnasium Hürth Bonnstrasse. 1 records from Berlese's Primitive Oribatid Mites. 42 records from Arachnologie ZMK. 203 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 12 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 2 records from Neue Oribatiden (Acari) aus Deutschland III. Suctobelba carcharodon n. sp. und Suctobelba prominens n. sp.. 6357 records from Distribution of foraminifera of sediment core GIK23258-2. 307 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 1 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 6 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 62 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 29983 records from Mycology herbarium, Tromsø Museum. 97 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 3 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas I. Zwei neue Arten der Gattung Suctobelba Paoli aus der Oberlausitz (DDR): Suctobelba scalpellata n. sp. und Suctobelba secta n. sp.. 19 records from Heinersdorfer Sumpfwiese. 291402 records from ARABEL - Arachnologia Belgica. 95 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 1 records from A new species of the genus Megophrys (Anura: Megophryidae) from Yunnan Province, China. 1 records from Laubuka parafasciata, a new cyprinid fish species (Teleostei: Cyprinidae) from Mizoram northeastern India. 348 records from Antarctic pycnogonids. 62776 records from MLZ Bird Collection (Arctos). 3 records from Redescription of Honduriella maxima Denmark & Evans (Acari: Mesostigmata: Phytoseiidae), description of a new species of Honduriella Denmark & Evans from the Amazonian Forest, and a modified characterisation of the genus. 1 records from Naturschutzgebiet Müchelholz (Mücheln). 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 13 records from Taxonomy of calcareous sponges (Porifera, Calcarea) sampled on artificial substrates of a recreational marina in the Tropical Northeastern Brazilian coast. 4 records from Two new species of freshwater, cave-dwelling crabs of the genus Neostrengeria Pretzmann, 1965, from Colombia (Crustacea: Decapoda: Pseudothelphusidae). 3 records from Wiese am Waldrand (Gurtweil). 148 records from Flora de los ecosistemas de la zona alta del río Coello (Tolima, Colombia). 4 records from A new small-sized Theloderma (Anura: Rhacophoridae) from Laos. 3 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 6 records from Two new species of Nemouridae (Plecoptera) from Vietnam. 638 records from MNA (Section of Genoa) - Marine Biological Samples. 12 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). I. Gracilipalpe, morchella and nigrum groups. 351 records from UWYMV Herpetology Collection (Arctos). 100678 records from Herbarium Senckenbergianum (FR) - Fungi. 2489 records from NU: KwaZulu-Natal Invasive Alien Species (1821-2011). 2000 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 8 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 2007 records from Plant specimens of Bihoro Museum. 84 records from Museu Paraense Emílio Goeldi - Myriapoda Collection. 944 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 51151 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 167 records from Taxonomic revision of the Palaearctic Tetramorium chefketi species complex (Hymenoptera: Formicidae).. 77 records from Empria and Monsoma in Japan. 22 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 321 records from Vegetación de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 18 records from Kinorhyncha specimens of Ryukyu University Museum (Fujukan). 395 records from Reptilia ZMK. 94251 records from Ibaraki Nature Museum, Vascular Plants collection. 5 records from Redescription of the poorly known crab spider Xysticus spasskyi (Araneae: Thomisidae). 3 records from Hylaperdina squamosa, a new species of Neotropical Lycoperdininae (Coleoptera, Endomychidae) from Brazil. 85277 records from University of Ghana - Ghana Herbarium. 5021 records from Sistematización de la colección entomológica y actualización de la colección del herbario CHIP del Instituto de Historia Natural y Ecología (IHNE), Chiapas. 16078 records from Digitization of plant specimens from Rhoen and Vogelsberg (FULD). 18 records from Three new generic records and descriptions of four new species of jumping spiders (Araneae, Salticidae) from Sri Lanka. 1 records from On a new species of Euchondrus Boettger, 1883 from Syria (Pulmonata: Enidae). 498736 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 110 records from Revision of Brada Stimpson, 1853, and Bradabyssa Hartman, 1967 (Annelida, Flabelligeridae). 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 8110 records from Catálogo de los equinodermos recientes de México (Fase II). 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 17 records from ScoliorhAPis stEPAnovi - new species of sea cucumber from the North-West Pacific (Holothuroidea: Synaptida: Chiridotidae: Taeniogyrinae) and some remarks on the genus ScoliorhAPis. 10898 records from Inventario de Hymenóptera; parasítica en México. 268160 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 4 records from Amazoniaseius imparisetosus n. sp., n. g.: an unusual new phytoseiid mite (Acari: Phytoseiidae) from the Amazon forest. 378 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 3 records from Two species of the conifera - subgroup of Triconia (Copepoda, Oncaeidae) from the northeastern equatorial Pacific, with a description of the unknown male of T. hirsuta. 48 records from Onuphi s and Mooreonuphis (Annelida: Onuphidae) from West Africa with the description of three new species and the reinstatement of O. landanaensis Augener, 1918. 1 records from A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber. 22516 records from MfN - Fossil Fish Collection. 1 records from Morphotaxonomic revision of species-groups of Simulium (Simulium) (Diptera: Simuliidae) in the Oriental Region. 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 15774 records from Insect Collection of Saitama Museum of Natural History. 750 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 1 records from A new edible cricket species from Africa of the genus Scapsipedus. 3 records from Triebesbach (Zeulenroda-Triebes). 11 records from List of leaf beetles (Coleoptera: Chrysomelidae) from Lagodekhi reserve with new records for Transcaucasia and Georgia. 3006 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 27 records from A new species of Astyanax (Teleostei, Characiformes, Characidae), with breeding tubercles, from the Paraná and Uruguay river basins.. 217 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 343 records from BIOLOGICAL SCIENCES DATA. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 8 records from Sandsitermes gen. nov., a new nasute termite genus from South America (Isoptera, Termitidae, Nasutitermitinae). 3425 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 963 records from University of Western Ontario Collection. 3 records from Wiese und Weide am Waldrand von Gusterath. 10 records from SyNoeca ilheeNsis sp. nov., a new social wasp (Hymenoptera, Vespidae, Polistinae) from Brazilian lowland Atlantic Forest. 5 records from Unna-Mühlhausen, Wiesen. 7 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 208 records from IBF Monitoring of Plant Galls. 267243 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 6 records from Cave-dwelling crabs of the genus Karstarma from lava tubes of the volcano ‘ Piton de la Fournaise’, in Réunion Island, with description of a new species and redescription of Karstarma jacksoni (Balss, 1934) from Christmas Island (Decapoda, Brachyura, Sesarmidae). 6 records from Discovery of two new Andean species of Scolomus (Townes & Townes), with a key to all known species (Hymenoptera: Ichneumonidae: Metopiinae). 408 records from Birds Specimens of Akita Prefectural Museum. 5 records from Certain species of Plecoptera from the headwater springs of National Integration River (São Francisco), Brazil. 14 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 1 records from Murcia acaroides. 216 records from Water striders (Heteroptera: Gerromorpha: Gerridae) of Romania with an update on the distribution of Gerris gibbifer and G. maculatus in southeastern Europe. 5 records from Redescription and phylogenetic analysis of the type species of the giant pill-millipede genus Sphaeropoeus Brandt, 1833 (Diplopoda, Sphaerotheriida, Zephroniidae). 52181 records from ANTARCTIC PLANT DATABASE. 63156 records from Field Museum of Natural History (Botany) Fungi Collection. 1 records from Nothrus echinatus. 19725 records from SJRP - Herbário de São José do Rio Preto. 2 records from A new species of Campylocia Needham & Murphy, 1924 (Ephemeroptera, Euthyplociidae) from Northern Brazil. 67 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 39 records from Nassau Mountain Expeditions 2005/2006/2010/2014. 95 records from Ibaraki Nature Museum, Amphibians and Reptiles collection. 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 1242 records from T. L. Hankinson Vertebrate Museum (EMU) Mammal Collection. 24 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 3 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 45 records from Morphological and genetic evolution in eastern populations of the Macrhybopsis aestivalis complex (Cypriniformes: Cyprinidae), with the descriptions of four new species. 736 records from Sistemática y biogeografía del género Xenosaurus (Squamata: xenosauridae). 7928 records from Scarabaeoidea y colección de tipos de la colección entomológica del Centro de Estudios en Zoología, Universidad de Guadalajara. 208 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 24 records from New species of the orb-weaving spider genus Chrysometa (Araneae, Tetragnathidae) from oak forests near of the Pico de Orizaba National Park (Veracruz, Mexico). 1952 records from ISM Ichthyology Collection. 38 records from Fourteen new species of Pseudisobrachium (Hymenoptera, Bethylidae) from Atlantic rain forest of Espírito Santo, Brazil.. 798 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 29 records from Unraveling the white-clothed Diestostemma Amyot & Serville: a taxonomic revision of the American sharpshooters of the D. bituberculatum complex (Hemiptera: Cicadellidae). 9 records from Three new brackish-water thalassocypridine species (Crustacea: Ostracoda: Paracyprididae) from the Ryukyu Islands, southwestern Japan. 5 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 27 records from A new species of crayfish in the genus Orconectes (Decapoda: Cambaridae) from the Tennessee River Drainage with comments on and key to members of the O. juvenilis Species Complex. 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 1 records from Formiciden aus dem Naturhistorischen Museum in Hamburg. II. Teil. Neueingaenge seit 1900 (PP). 142891 records from The Himalayan Uplands Plant database (HUP Version 1). 1 records from Artenvielfalt auf dem Schulgelände. 500808 records from Neptune Deep-Sea Microfossil Occurrence Database. 76380 records from DMNH Birds. 1014 records from Database on reference specimens for medicinal plants of the Euphorbiaceae family, conserved at the CNARP herbarium. 31015 records from National Museum of Natural Science. 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 1 records from Zetes flavipes. 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 3 records from Amended diagnosis and redescription of Pristimantis marmoratus (Boulenger, 1900) (Amphibia: Craugastoridae), with a description of its advertisement call and notes on its breeding ecology and phylogenetic relationships. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 17 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 322 records from Collections ichtyologiques et herpétologiques (BOUM). 10 records from A new wobbegong shark, Orectolobus hutchinsi n. sp. (Orectolobiformes: Orectolobidae) from southwestern Australia.. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 13 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 91 records from Notes on species of the genus Chlaenius Bonelli, 1810 (Coleoptera: Carabidae, Chlaeniini) from four agro-climatic zones of Rajasthan, with description of two new species. 141 records from La collection Gilles Becquet (BOUM). 65903 records from Norwegian Lepidoptera working group. 2 records from A new cicada species of Psalmocharias Kirkaldy feeding on an Ephedra plant from China (Hemiptera: Cicadidae). 26 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 38876 records from Pteridophyta collection of Museum of Natural and Environmental History, Shizuoka. 4 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 9062 records from Northern Biodiversity Program Coleoptera (2010-2011). 36 records from Validity of Psammoperca datnioides Richardson 1848 and redescriptions of P. waigiensis Cuvier in Cuvier & Valenciennes 1828 and Hypopterus macropterus (Günther 1859) in the family Latidae (Perciformes) from the Indo-West Pacific. 2 records from A new Panolis Hübner, [1821] species from Vietnam (Lepidoptera, Noctuidae, Orthosiini). 5 records from New records of Synallactes virgulasolida Massin & Hendrickx, 2010 (Echinodermata: Holothuroidea) from the eastern Pacific. 13 records from Systematic notes on some leptomedusa species with a description of Neotima galeai n. spec. (Hydrozoa, Cnidaria). 1004 records from National Museum of Marine Biology and Aquarium. 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 50 records from Neotropical osmylids (Neuroptera, Osmylidae): Three new species of Isostenosmylus Krüger, 1913, new distributional records, redescriptions, checklist and key for the Neotropical species. 6774 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleopalynology National Collection (BAPal). 270 records from bmhs_weatherheadshell_collection. 6 records from Immature stages of the genus Oxythyrea (Coleoptera: Scarabaeidae: Cetoniinae) with a key to third instar larvae, and notes on the biology of the genus. 1 records from Sächsische Schweiz (Pfaffenstein). 234 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 1 records from Nemertean specimens of Ryukyu University Museum (Fujukan). 6 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 285727 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 35 records from Anthomyiidae, Fanniidae and Muscidae (Diptera) from the Juan Fernández Archipelago (Chile): 60 years after Willi Hennig’s contributions. 2531 records from Inventario florístico de Tetipac y sus alrededores (Sierra de Taxco). 220 records from Living Cirripedia. 11 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 2 records from Notes on the biology and distribution of the tribe Agallissini in North America (Coleoptera: Cerambycidae: Cerambycinae). 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 15637 records from CCBER Herpetology Collection. 23 records from New species of Pseudoscorpiones (Arachnida) from tree hollows in a Mediterranean oak forest in Spain. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 1 records from Roter Berg Werdau (Leubnitz). 36 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 506 records from Base de datos sobre los hongos anamorfos de restos de vegetales del bosque mesófilo del estado de Veracruz. 15 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 1 records from Mauernacker (Wettsaasen). 4 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 1 records from New species of the anthiadin genus Sacura (Perciformes: Serranidae) from the Andaman Sea. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 7 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 85 records from A new distinctive species of Barydesmus (Diplopoda, Polydesmida, Platyrhacidae) from Ecuador, with an annotated bibliographical checklist of the American Platyrhacidae. 18 records from New genus to science of Meconematinae (Orthoptera: Tettigoniidae) from China with description of two new species and proposal of one new combination. 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 2 records from Neue Milbenarten aus Kärnten. 1 records from Nothrus biverrucatus. 8 records from A review of the taxonomy and osteology of the Rhombophryne serratopalpebrosa species group (Anura: Microhylidae) from Madagascar, with comments on the value of volume rendering of micro-CT data to taxonomists. 6780 records from Herpetofauna del Estado de Veracruz. 56964 records from Entomology Collection at the Natural History Museum of Utah. 1 records from A PArtial Skeleton of the Tyrannosaurid Dinosaur Aublysodon from the Upper Cretaceous of New Mexico. 11 records from Visual Plants (144.41.33.158) - Herbarium specimens from "LOJA" Ecuador. 1 records from A new species of Cladotanytarsus (Lenziella) from Oregon supports the systematic concept of the subgenus (Diptera: Chironomidae). 890 records from Inventarios florísticos en Baja California Sur (II): Vegetación costera. 2 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 26841 records from MSUM Ichthyology and Herpetology Collections. 1143 records from Herpetofauna de la región El Huizache, San Luis Potosí. 3 records from Two new records of palm species for Gabon: Sclerosperma profizianum Valk. & Sunder. and Eremospatha quiquecostulata Becc.. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 371 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 25 records from Two new species of the gobiid fish Trimma from the coral reefs of the western Pacific Ocean (Pisces; Perciformes; Gobioidei).. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 4 records from Two new species of Psephenops Grouvelle (Coleoptera: Byrrhoidea: Psephenidae) from Panama. 8 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 126 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 184807 records from Tiroler Landesmuseum Ferdinandeum. 89 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 6 records from Skeletal Adaptations of Ornitholestes, Struthiomimus, Tyrannosaurus. 68 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 1 records from A new species of the genus Comaroma in China (Araneae: Anapidae). 5 records from Evaluación de la situación de Tillandsia mauryana en el Apéndice II de la CITES, según su estado de conservación y comercio. 78 records from Mammals (GNHM-MM). 3 records from The first record of the genus Desertoniscus Verhoeff, 1930 (Isopoda, Oniscidea, Agnaridae) from Europe, with the description of a new species. 2 records from Description of the female and egg of Phantasca phantasma (Westwood, 1859) (Phasmatodea: Diapheromeridae: Diapheromerinae). 102 records from Twenty new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental Region. 158 records from The genus Anisoscelis Latreille (Hemiptera: Heteroptera: Coreidae: Coreinae: Anisoscelini): new species, taxonomical arrangements, distributional records and key. 3 records from Notes on west Palaearctic species of the genus Trigonurus Mulsant, 1847 (Coleoptera: Staphylinidae: Trigonurinae). 12 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 1 records from Bryozoans Specimens of Akita Prefectural Museum. 1000 records from Plant specimens of Natural History Museum, Kishiwada City. 2168 records from Inventario avifaunístico de las áreas focales Zoh-Laguna y La Montaña en el corredor biológico mesoamericano Sian Ka'an- Calakmul, México. 200 records from Bird specimens of Kushiro City Museum. 3 records from F. L. de Castelnau’s Norman River fishes housed in the Macleay Museum, University of Sydney. 1 records from One new species of Amphinemura and description of the female of A. ancistroidea Li & Yang (Plecoptera: Nemouridae) from Guangxi Zhuang Autonomous Region of southern China. 9 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 7217 records from CNMT - Herbário Centro Norte Mato Grossense. 22 records from Thirteen new records of ferns from Brazil. 8 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 351 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 936 records from RMT Trawl catch from the 1982/83 V2 ADBEX I voyage. 679 records from Collection Hydrozoa - ZSM München. 40 records from Two new cichild species Neolamprologus (Teleostei: Cichlidae) from Lake Tanganyika, East Africa.. 22 records from The eel genus Macrocephenchelys (Anguilliformes: Congridae) in Taiwan, with description of a new species. 2 records from Redescription of the Amazonian tiny tree toad Amazophrynella minuta (Melin, 1941) (Anura: Bufonidae) from its type locality. 202563 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 17520 records from Royal Museum of Central Africa - True Fruit Flies (Diptera, Tephritidae) of the Afrotropical Region (ENBI wp13). 1 records from On some Haploops species collected in the North Atlantic Ocean with the description of Haploops islandica n. sp. (Crustacea: Gammaridea: Ampeliscidae) [Contribution to the knowledge of the Haploops genus. 8.]. 188368 records from Geneva Herbarium – General Collection (G). 34 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 271 records from Vegetación de los remanentes de bosque andino, municipio de San Francisco (Cundinamarca). 31394 records from NCSM Vertebrate Paleontology Collection. 790 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core PS1906-1 (Table 9). 4792 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 67 records from Characidium longum (Characiformes: Crenuchidae), a new fish from Venezuela.. 367 records from QLD DERM Coastal Bird Atlas (Trial). 3 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 51054 records from SPSF - Herbário Dom Bento José Pickel. 34 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 15 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 71 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 136061 records from Arizona State University Vascular Plant Herbarium. 1872 records from Herbier National de Guinée (HNG) (BID-AF2015-0066-REG). 39 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 2 records from Out of the Neotropics: newly discovered relictual species sheds light on the biogeographical history of spider ants (Leptomyrmex, Dolichoderinae, Formicidae). 651 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 6071 records from EDIT - ATBI in Gemer area (Slovakia). 14 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 3861038 records from Natural History Museum (London) Collection Specimens. 4 records from Ried und Sand - Artenvielfalt durch Beweidung. 22053 records from UTEP Vertebrates. 2 records from AKG-Gelände (Bensheim). 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 5 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 4926 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 6 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 6 records from Six new and one known species of Geomonhystera (Nematoda, Monhysteridae) from moss, an epiphytic plant and soil in México and Ecuador. 19 records from Distribution of planktic foraminifera of sediment core GIK23059-3 at stadium 5.5. 32 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 2532 records from Visual Plants (144.41.33.158) - Herbarium specimen from the Estacion Scientifica San Francisco, Southern Ecuador. 16128 records from Colección Ictiológica del Instituto Alexander von Humboldt. 33 records from The Gomphocerinae Tarbinsky, 1932 (Orthoptera: Acrididae) fauna of the Turkish Thrace. 7 records from Two new species of Quichuana Knab (Diptera: Syrphidae) from the paramo ecosystems in Colombia. 137535 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 159 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 1510 records from Collection botanique Jaubert et Saul (BOUM). 33 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 6 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 1 records from Lebensraum Gesamtschule (Langerwehe). 1 records from Pelops tardus. 86 records from Modelación de la distribución real y potencial de especies de dos géneros de Mimosoideae: Mimosa y Prosopis (Leguminosae) en México. 2905 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-9. 4 records from Two new species of Willowsia (Collembola: Entomobryidae) from Guizhou Province, China. 18094 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 4 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 1350 records from ENBI WP 13 Martius C. F. P. von Collection subset (Muenchen). 1 records from Riedkanal Bötzingen. 19 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 3 records from New findings of Hexalona-branch representatives in Brazil, with a description of Prenda gen. nov. (Crustacea: Anomopoda: Aloninae). 7 records from One new species and one newly recorded species of Cyllodes Erichson from China (Coleoptera: Nitidulidae: Nitidulinae). 19021 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) planctónicas más frecuentes en el Golfo de California. 22 records from A revision of the genus Disparalona (Cladocera, Chydorinae) in South America. 2140 records from Captive Primate Specimens of Japan Monkey Centre. 11 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 18 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 36 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 4621 records from Códigos de barras de la vida en peces y zooplancton de México. 99 records from Ant-like stone beetles on the roof of the world. Cephenniini of Nepal and Bhutan (Coleoptera, Staphylinidae, Scydmaeninae). 30 records from On the taxonomy of the genera Planovalvata Dubatolov & Kishida, Stigmatophora Staudinger and Pseudomiltochrista Dubatolov & Bucsek, with description of one new species (Lepidoptera, Erebidae, Arctiinae, Lithosiini). 62324 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 6 records from New data on the distribution of aquatic bugs (Hemiptera) from eastern Morocco with notes on chorology. 5 records from Loricifera - SMF. 100970 records from Canadian Museum of Nature Bird Collection. 5 records from New taxa and notes of katydids from the tribe Meconematini (Orthoptera: Meconematinae) from Brunei Darussalam (Part 2). 497 records from Especies de Leptohyphes (Insecta: Ephemeroptera: Leptohyphidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 3 records from Cyrtodesmus baerti, n. sp., a cryptic millipede from the Galápagos Islands, Ecuador (Diplopoda, Polydesmida, Cyrtodesmidae). 1258 records from CMC_ornithology_GRC. 13 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 1 records from Orthochaetes estrelanus sp. n., a new species from northern Portugal and new records of other Styphlini (Coleoptera, Curculionidae).. 5 records from Three new species of Lyssomanes HENTZ, 1845 from Peru (Arachnida: Araneae: Salticidae). 47 records from Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae). 18 records from Nivalios gen. nov. (Hemiptera: Fulgoromorpha: Flatidae), first record of the tribe Nephesini from China. 391 records from An updated checklist of aquatic plants of Myanmar and Thailand. 1702 records from BioGIS - Bryophytes - HUJ collections. 437 records from Chilopoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 752 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 28 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 10 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 14591 records from Collection Coleoptera SMF. 672 records from Colección de Entomología - Curculionidae. 6 records from Taxonomy of the European Pied Flycatcher Ficedula hypoleuca (Aves: Muscicapidae). 4 records from Spießwoogtal / Königsbruch (Fischbach). 30 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 13 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 94 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Mollusca (ZUFMS-MOL). 19739 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 3 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 423 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 16522 records from Shellfish specimens of the Nishinomiya Shell Museum, Japan. 2645 records from KTU Pteridophyta. 6237 records from Plecoptera. 13 records from A new species of Hippopsis Lepeletier & Audinet-Serville, 1825 from Panama and key to species (Coleoptera, Cerambycidae, Lamiinae). 52 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 9 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 1 records from A new species of Ferneiella from the Eocene French amber (Diptera: Scatopsidae). 3 records from Benthic hydroids (Cnidaria: Hydrozoa) from off George V Coast (East Antarctica). 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 3 records from Two new species of Darnini (Hemiptera: Membracidae) from Colombia and Peru. 196 records from Collection des mammifères d'Auvergne. 500 records from Plant specimens of Oiso Municipal Museum. 3948 records from (Supplement 1) Relative abundance of planktic foraminifera in sediments of the last 560 kyr of ODP Hole 165-999A, Caribbean Sea. 12 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 2130 records from database_hemiptera. 16469 records from Arbeitsgemeinschaft Heuschrecken Österreichs. 43 records from bmhs_beetle_collection. 53 records from Unraveling Ocyptamus and the Baccha legacy (Diptera: Syrphidae): redefinition of groups and new species descriptions. 25 records from Morphologische Daten von Natrix. 8 records from Three new species of seasonal killifishes of the Simpsonichthys antenori species group (Teleostei: Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, Brazil.. 118 records from Collection botanique Lamy de la Chapelle E. (BOUM). 174194 records from Mississippi Entomological Museum. 277 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 9 records from Key to the currently recognized species of Limnias Schrank, 1803 (Rotifera, Monogononta, Gnesiotrocha, Flosculariidae). 4 records from Schulgarten Fichteschule. 8 records from The spiny theridiid genus Meotipa Simon, 1895 in India, with description of a strange new species with translucent abdomen and a phylogenetic analysis about the genus placement (Araneae, Theridiidae). 2 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 53 records from On the taxonomy of southern South American species of the wolf spider genus Allocosa (Araneae: Lycosidae: Allocosinae). 5 records from Dolichopodidae of riverbeds and springs in Croatia with an updated checklist of Croatia (Diptera). 9 records from A new genus and species of entocytherid ostracod (Ostracoda: Entocytheridae) from the John Day River Basin of Oregon, U. S. A., with a key to genera of the subfamily Entocytherinae. 5 records from A new species of Rhigognostis (Lepidoptera, Plutellidae) from the Canary Islands. 6065 records from LISU Herbario Angola. 4749 records from CNAC/Coleccion Nacional de Acaros. 15291 records from The Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 78575 records from AM: Freshwater Invertebrates (1900-2005). 2 records from Intraspecific variation in adult Uvitellina iraquensis Dronen, Ali & Al-Amura, 2013 (Cyclocoelidae: Haematotrephinae) from two collection sites of white-tailed lapwing, Vanellus leucurus (Lichtenstein) (Charadriiformes: Charadriidae), in Iraq. 628 records from hauterivian_echinoids_of_the_paris_basin. 44 records from Description of the larvae and pupae of eight species of the tribe Sitonini Gistel, 1848 (Coleoptera, Curculionidae) from Central Europe. 16 records from Proposal of Kupiuka and Plesiopiuka, two new genera of jumping spiders from Brazil (Araneae: Salticidae: Heliophaninae). 70 records from Coccoliths in sediment core GIK23065-3. 251 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 895 records from Códigos de barras de hongos ectomicorrízicos de localidades selectas del neotrópico mexicano. 6 records from Two new records and one new species of the genus Apelaunothrips from China (Thysanoptera: Phlaeothripidae). 11392 records from Danish Plant Bugs (Miridae). 101 records from The genus Setodes Rambur (Trichoptera, Leptoceridae) in Japan. 18571 records from ZUEC-POL - Coleção de Polychaeta do Museu de Zoologia da UNICAMP. 1004 records from Actualización de la base de datos de la Colección nacional mexicana de cultivos microbianos. 44 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 71 records from Morphology and taxonomy of the orb-weaving spider genus Mecynogea, and a peculiar species of Argiope (Araneae, Araneidae). 27 records from Two new dragonflies (Odonata: Anisoptera) from the Miocene of Carinthia (Austria). 10 records from Three new genera and three new species of Nearctic Lasiopteridi (Diptera: Cecidomyiidae: Cecidomyiinae) from Asteraceae and Caprifoliaceae, and the tribe Rhopalomyiini subsumed under Oligotrophini. 16 records from A review of New World Malaxa (Hemiptera: Fulgoroidea: Delphacidae). 6077 records from Vascular plant specimens of Iida City Museum. 3 records from Three New Spiders of the Families Clubionidae, Liocranidae and Gnaphosidae (Arachnida, Araneae) from Vietnam. 44802 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 62 records from Revision of early taxa of Australian gall midges (Diptera: Cecidomyiidae). 17 records from New species, new records, and new collection data of Rhyacophila from China (Trichoptera: Rhyacophilidae). 59 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 20576 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Ornithology National Collection (MACNOr). 6 records from Pushing the limits - two new species of Pteromalus (Hymenoptera, Chalcidoidea, Pteromalidae) from Central Europe with remarkable morphology. 3 records from Steinbruch Mainz-Weisenau, 3. Jahr. 1834 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 15 records from Additions to the ichthyofauna of the Tristan da Cunha Group, South Atlantic Ocean.. 3251 records from Inventario florístico de la Sierra de Huautla, Morelos. 18 records from Revision of the genus Centrophorus (Squaliformes: Centrophoridae): Part 2 - Description of two new species of Centrophorus and clarification of the status of Centrophorus lusitanicus Barbosa du Bocage & de Brito Capello, 1864. 31 records from Notes on the genus Conocephalus Thunberg, 1815 (Orthoptera: Tettigoniidae: Conocephalinae) in Southwest China with description of one new species. 1 records from Zielbach (Töll). 622 records from Inventario de sanguijuelas (Annelida: Clitellata Hirudinea) de México, con énfasis en las especies del centro de México. 203849 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 30 records from Revision of Hestiasulini Giglio-Tos, 1915 stat. rev. (Insecta: Mantodea: Hymenopodidae) of Borneo, with description of new taxa and comments on the taxonomy of the tribe. 6 records from Two new species of Guyruita Guadanucci et al., 2007 (Araneae, Theraphosidae) from Brazil. 10 records from New species of Graphocaecilius Enderlein (Psocodea: ‘ Psocoptera’: Lachesillidae) from Colombia. 2 records from A new species of Polyipnus (Stomiiformes: Sternoptychidae) from the Western South Pacific. 892 records from (UTC) University of Tennessee Mammals Collection. 128095 records from University of Michigan Museum of Zoology, Division of Mammals. 21773 records from Birds Specimens. 46318 records from Banco de datos florísticos del Herbario CHAP. 6 records from Contributions to the study of Idiocerinae (Homoptera: Auchenorrhyncha: Cicadellidae) of Central Asia with notes on synonymy. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 4 records from Redescription of Micaria beaufortia (Araneae, Gnaphosidae), with notes on Afrotropical Micaria. 2052 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 92 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 18911 records from DMNS Mammal Collection (Arctos). 6959 records from Bird collection NTNU University Museum. 179 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna”. 11169 records from Akita Prefectural Museum, Hiroki Watanabe Collection. 1 records from A new species of the genus Pachytriton (Caudata: Salamandridae) from Hunan and Guangxi, southeastern China. 58 records from Newhaven Sanctuary observations. 3 records from A new species of Hebrus (Hemiptera: Heteroptera: Hebridae) from Argentina. 2281 records from Relative abunances of benthic foraminifera in Late Oligocene to Miocene sediments of ODP Hole 121-757B from the southeastern Indian Ocean (Appendix Table 1). 6 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 82 records from Taxonomic review of the ladybird genus Sticholotis from China (Coleoptera: Coccinellidae). 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 785 records from Colección de Mamíferos Marinos del Centro Nacional Patagónico. 26835 records from Herbario Pontificia Universidad Javeriana. 5 records from Cryptic species among bumblebee mimics: an unrecognized Hemaris hawkmoth (Lepidoptera: Sphingidae) in eastern North America. 7 records from Synopsis of the shore bugs of China (Hemiptera: Heteroptera: Leptopodomorpha: Saldidae). 11 records from A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae). 181 records from Colección Ornitológica Museo de Ciencias Naturales “Lorenzo Scaglia" (MMPOr) Mar del Plata, Argentina.. 458 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 42 records from The genus Cryptotendipes Beck et Beck in Florida, with the description of a new species (Diptera: Chironomidae: Chironominae). 192 records from ENBI-Dataset of GART-GloBIS. 2568 records from Fish (NHMK-PI). 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 2427 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 174 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 106 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 3 records from Two new species of Polana (Hemiptera: Cicadellidae: Iassinae: Gyponini) and redescription of Polana (Striapona) desela. 1 records from Schulteich/Tümpel Thor-Heyerdahl-Gymnasium (Kiel). 2 records from Schizopyga alinae, a genus of pimpline parasitoid wasps (Hymenoptera: Ichneumonidae: Pimplinae) new to the Afrotropical region. 39 records from Coccoliths in sediment core GIK23059-2. 2 records from A new record of the genus Discoelius Latreille, 1809 (Hymenoptera: Vespidae: Eumeninae) from Northern Vietnam with description of two new species. 9103 records from The Fungal Collection at the Botanische Staatssammlung München. 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 1030627 records from Phanerogamic Botanical Collections (S). 844 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 12337 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 47 records from A study on the genus Stenus Latreille from Zhuji City of Zhejiang, East China (Coleoptera, Staphylinidae). 14202 records from Herbarium specimens of Hokkaido University Museum. 4 records from Anisops sardeus Herrich-Schaeffer, 1849: first records from Hungary (Heteroptera: Notonectidae). 1 records from A New Genus and Species of Blind Sleeper (Teleostei: Eleotridae) from Oaxaca, Mexico: First Obligate Cave Gobiiform in the Western Hemisphere. 174 records from Lichen specimens of Okinawa Prefectural Museum & Art Museum. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 488 records from Anfibios y reptiles del municipio de Cuetzalan del Progreso, Puebla. 19 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 3 records from New species of Lonchaeidae (Diptera) from Switzerland and Serbia with arevised checklist of the Swiss fauna. 8 records from Gurgltal (Tarrenz). 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 1 records from Papilio Sticheli nov. spec. aut subsp.. 2 records from A new species of Aphelocheirus (Hemiptera: Heteroptera: Aphelocheiridae) from Morocco. 19 records from Database on reference specimens for medicinal plants of the Araceae family, conserved at the CNARP herbarium. 48 records from A new species of Metrobates Uhler, 1871 (Hemiptera: Heteroptera: Gerridae) from Colombia. 895 records from Distribución, abundancia y selección de hábitat de especies de aves amenazadas y en peligro de extinción en los bosques de montaña de Chiapas. 769 records from Digital Florula - Palo Verde Biological Station. 2824 records from Fundación Miguel Lillo - Colección Invertebrados. 54 records from A catalog of Acroceridae (Diptera) from Chile. 22 records from South American Antarctic Marine Biodiversity Literature. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 2532 records from Collection Messelpaläobotanik SMB. 3 records from The dark side of pumpkin toadlet: a new species of Brachycephalus (Anura: Brachycephalidae) from Serra do Brigadeiro, southeastern Brazil. 73 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Ben Hell. 32 records from Australian Marsh Beetles (Coleoptera: Scirtidae). 9. The relations of Australasian Ypsiloncyphon species to their Asian congeners, additions, mainly to Petrocyphon and Prionocyphon, and a key to Australian genera of Scirtinae. 6 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 345 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 1 records from Callogorgia lucaya sp. nov., a new species of deep-sea Primnoidae (Anthozoa: Octocorallia) from the western Atlantic. 871 records from FLORA REGIONAL Y OTROS PAÍSES. MMHNSR 2018. 19 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 23 records from Many things come in small packages: Revision of the clawless geckos (Crenadactylus: Diplodactylidae) of Australia. 10 records from Meadow katydids (Orthoptera: Tettigoniidae: Conocephalini) from the Central-West Region of Brazil: Morphological, bioacoustic and cytogenetic study. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 5 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 7887 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 110 records from Historical review, catalog of type specimens and online database of the ichthyology collection of the Instituto de Ciencias Naturales of the Universidad Nacional de Colombia (ICN-MHN). 34 records from ZUEC-EPH - Coleção de Ephemeroptera do Museu de Zoologia da UNICAMP. 84 records from A revision of the spider genus Raveniola (Araneae, Nemesiidae). I. Species from Western Asia. 104 records from Mammalogie ZMK. 10 records from Checklist of the Free-Living Marine Nematodes of the Iberian Peninsula (north east Atlantic). 750 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 2063 records from Flora d'Andorra. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 4 records from Four new earthworm species of Kazimierzus Plisko, 2006 (Clitellata, Kazimierzidae). 6010 records from Computarización de la colección de insectos de la Universidad de Morelos, CIByC, UAEM. 15 records from Conringia orientalis. 11 records from A new genus and three new species of nemacheilid loaches from northern Irrawaddy drainage, Myanmar (Teleostei: Cypriniformes). 1 records from Erpetogomphus oxybelis sp. nov. from Veracruz, Mexico (Odonata: Gomphidae). 3 records from A new subfamily, Styracurinae, and new genus, Styracura, for Himantura schmardae (Werner, 1904) and Himantura pacifica (Beebe & Tee-Van, 1941) (Chondrichthyes: Myliobatiformes). 1 records from A new species of the genus Paratus Simon (Araneae: Liocranidae) from Thailand. 2300 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México. 189 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 5448 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 73 records from (Appendix A) Sea surface temperture reconstruction for ODP Hole 117-723A. 1 records from Celaeno obsoleta. 25 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 272947 records from Allan Herbarium (CHR). 254256 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from Pinguisoperla, a new fossil genus of Perlidae (Insecta: Plecoptera) from mid-Cretaceous Burmese amber. 3 records from Miltochrista wangmini, a new species from China (Lepidoptera, Erebidae, Arctiinae). 4 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 3984 records from Fungal Collection of Natural History Museum and Institute, Chiba. 14275 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 27 records from Two new species of freshwater crayfish of the genus Faxonius (Decapoda: Cambaridae) from the Ozark Highlands of Arkansas and Missouri. 35 records from Review of the genus Typhloiulus Latzel, 1884 in the Dinaric region, with a description of four new species and the first description of the male of Typhloiulus insularis Strasser, 1938 (Diplopoda: Julida: Julidae). 3 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 7 records from First record of Psilacrum Becker 1912 (Chloropidae, Diptera) from Brazil, with the description of a new species. 18567 records from Cercle des mycologues de Montréal Fungarium (CMMF). 265 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1244-2. 27 records from New records in vascular plants alien to Kyrgyzstan. 3 records from Aquatic microdrile Oligochaeta (Annelida, Clitellata): New nominal taxa and combinations since 1984. 5 records from Cladocera from the Upper Xingu River Basin with the description of a new genus of the Chydoridae (Crustacea: Branchiopoda: Anomopoda). 3 records from Vorderer Tiergarten (Dessau). 4 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 1 records from A new genus and species of congrid eel from the Philippines (Anguillliformes: Congridae: Bathymyrinae). 77258 records from CSIC-Real Jardín Botánico-Colección de Hongos (MA-Fungi). 233 records from Colección Mastozoológica Universidad de los Llanos. 5428 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 2 records from Warnowtal (Rostock). 62 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 27830 records from Marie-Victorin Herbarium (MT) - Bryophytes. 330 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 54 records from Jeff Ogden Collection. 3 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 67 records from Neostasina gen. nov., a new genus of huntsman spiders from the Neotropical region (Araneae, Sparassidae, Sparianthinae). 70 records from A new species and new country records for the genus Leptobium Casey in the Palaearctic Region (Coleoptera: Staphylinidae: Paederinae). 181 records from Dinoflagellate cysts from sediment core PS1295-4. 11 records from Nematomorpha from Hong Kong and description of a new species from Malaysia. 2 records from Isoperla vjosae sp. n., a new species of the Isoperla tripartita group from Albania (Plecoptera: Perlodidae). 2 records from Mauervegetation,Flechten und anderes. 2 records from Feriendorf des Kreises Groß-Gerau Ober-Seemen/Gedern. 83 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 186 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 181 records from New data on spiders (Aranei) from the Maritime Province, Russian Far East. 96726 records from Buffalo Society of Natural Sciences Clinton Herbarium. 1 records from Schistobrachia kabata sp. nov. (Siphonostomatoida: Lernaeopodidae) from rajiform hosts off South Africa. 3239 records from Arthropods from Praia da Vitória (Terceira, Azores, Portugal). 2 records from Trachelus stipa (Hymenoptera: Cephidae), a new stem sawfly from Central Anatolia associated with feather grass (Stipa holosericea, Poaceae). 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 64 records from Revision of the Barsine cardinalis - anomala ' species-complex' (Lepidoptera, Erebidae, Arctiinae). 50 records from Université Pédagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 946 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 45 records from A checklist of the Iranian Mordellidae (Coleoptera: Tenebrionoidea). 978 records from Sammlung Eggers Westindien Herbarium Hamburgense HBG. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 9902 records from DSMZ Bacteria. 240933 records from CAS Entomology (ENT). 13292 records from CNIN/Thysanoptera. 4126 records from Naturalis Biodiversity Center (NL) - Pisces. 150 records from Molluscan fauna of Gueishan Island of Taiwan. 32 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 34 records from Species delimitation in the Gehyra nana (Squamata: Gekkonidae) complex: cryptic and divergent morphological evolution in the Australian Monsoonal Tropics, with the description of four new species. 2968 records from John Clayton's Fijian Moth Collection. 2166 records from Prime Hoverfly (Insecta: Diptera: Syrphidae) Areas (PHA) as a conservation tool in Serbia. 87 records from The genus Phlesirtes Bolivar, 1922 (Orthoptera: Tettigoniidae: Conocephalinae, Conocephalini; Karniellina), a review of the genus with data on its bioacoustics and the description of new species. 2970 records from Data mobilized by the National Herbarium of Benin in the framework of the JRS Biodiversity project of Benin. 386 records from (Table 3) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704A. 320 records from Myxomycetes collection of the University of Eastern Finland. 47 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 348 records from (Appendix 6) Benthic foraminifera at termination II in sediment core PS1906-2 in the Greenland Sea. 2389 records from PAMP-tracheo: Vascular plants in Pamplona Basin (Navarra, Spain). Undergraduate thesis, D. Vicente. 897 records from Insect Ichneumon fly (KIDR-IN). 338 records from Fishes in MZNA-VERT: cyprinid and salmonid communities in the rivers Erro and Urederra (Spain). PhD project, Cristina García-Fresca. 3 records from A new species of sponge-dwelling Elacatinus (Pisces: Gobiidae) from the western Caribbean.. 19 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 66714 records from DBG Kathryn Kalmbach Herbarium. 14009 records from Collection Trichoptera - SMF. 1701 records from MfN Fish Collection, Zoology. 33905 records from Insect specimens of Tochigi Prefectural Museum. 2 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 21 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 214 records from Bases de datos de Tanaidaceos (Crustacea: Peracarida) del Mar Caribe mexicano y Poliquetos pelágicos del Golfo de México y Mar Caribe mexicano. 207 records from (Table 5) Carbon flux, paleoproductivity, relative abundance of foraminifera on sediment core PS2138-1. 685 records from Bulk components and planktonic foraminifera of sediment core GeoB7139-2. 3 records from A new skipper from China: Notocrypta ariannae n. sp. (Lepidoptera, Hesperiidae). 10 records from Supplement to the knowledge of the genus Batraxis Reitter (Coleoptera: Staphylinidae: Pselaphinae) of China. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 97366 records from Arizona State University Hasbrouck Insect Collection. 13570 records from Royal Botanical Gardens Herbarium. 7127 records from MEXU/Asclepiadaceae. 430 records from Collection Strepsiptera SMF. 7582 records from Tropical epiphyte diversity under human impact ? Comparing primary forests, secondary forests, and forest fragments in Ecuador - Otonga. 5 records from Description of two new species of the genus Automate De Man, 1888 (Crustacea: Decapoda: Caridea) from the South China Sea. 12 records from An inordinate fondness for Osedax (Siboglinidae: Annelida): Fourteen new species of bone worms from California. 218 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 2 records from A new ant species of the Leptogenys sulcinodagroup (Hymenoptera: Formicidae) from Saudi Arabia. 148 records from BioAcoustica: Wildlife Sounds Database. 40 records from Records of Giant Silkmoths (Saturniinae) from Vermont Collections and 2002-2007. 5 records from A new Candonopsini (Ostracoda) genus from subterranean waters of New South Wales (Australia). 2544 records from Freshwater fishes of Greece. 197 records from TransForest vegetation data. 21 records from Studies in Guatemalan Ensifera: New Glaphyrosoma species (Orthoptera: Anostostomatidae) and additional data for other described species. 2 records from A remarkable new plant bug genus and species (Hemiptera, Heteroptera, Miridae, Deraocorinae) from the Australian wet tropics. 252 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 3 records from Callianassa ehsani, a new species of Callianassidae (Crustacea, Decapoda, Axiidea) from Gulf of Oman, Iran. 1268 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 2522 records from NMU Mammal Collection (Arctos). 101 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 3 records from Species diversity of Rhinebothrium Linton, 1890 (Eucestoda: Rhinebothriidea) from Styracura (Myliobatiformes: Potamotrygonidae), including the description of a new species. 1 records from Protozoa ZMK. 5 records from A new genus and species of Sclerodactylidae (Echinodermata: Holothuroidea: Sclerothyoninae) from the Pacific coast of Panama, and assignment of Neopentamera anexigua to Sclerothyoninae. 1 records from A new riparian Mantidactylus (Brygoomantis) frog from the Tsaratanana and Manongarivo Massifs in northern Madagascar. 2 records from A new limestone-dwelling leaf-toed gecko (Gekkonidae: Dixonius) from Khao Sam Roi Yot massif, peninsular Thailand. 10 records from Review of the cave cricket genus Tamdaotettix Gorochov with a new species and some new descriptions (Orthoptera: Rhaphidophoridae, Aemodogryllinae). 396 records from (Appendix 1) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2042. 1 records from Dörnberg. 202 records from The Crematogaster (Hymenoptera, Formicidae, Myrmicinae) of Costa Rica.. 23048 records from Herpetology Collection. 6746 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 2 records from Arthropoden aus südotsalpinen Höhlen gesammelt von Karl Strasser. 4. Aufsatz. 2 records from Afroanomalia pseudoclistopyga, a new genus and species of pimpline parasitoid wasp (Hymenoptera: Ichneumonidae: Pimplinae) from the Afrotropical region. 1 records from Nouveautes sur la faune des Chilopodes de Yougoslavie. 122 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 88986 records from URM - Herbário Pe. Camille Torrand. 540 records from Streamlining the use of BOLD specimen data to record species distributions: a case study with ten Nearctic species of Microgastrinae (Hymenoptera: Braconidae). 2 records from Macrozoque hoplandrioides (Coleoptera: Staphylinidae: Aleocharinae), a new genus and species of false Lomechusini from México. 3 records from Species of Wadicosa (Araneae, Lycosidae): a new species close to W. quadrifera (Gravely) from the Western Ghats, India. 8111 records from ZMMU MSU, White Sea Branch. 3 records from Dactylogyrids (Monogenea) parasitic on marine fish from Peru including the description of a new species of Haliotrema Johnston & Tiegs, 1922 and two new species of Parancylodiscoides Caballero & C. & Bravo-Hollis, 1961. 7 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 1268 records from (Appendix A) Ostracod taxa from IODP Site 306-U1314. 71 records from Review of the Poecilimon (Poecilimon) zonatus species group and description of new species from Turkey with data on bioacoustics and morphology (Orthoptera: Phaneropterinae). 561 records from Colección de Vertebrados (naturalizados y en fluido) del Departamento de Zoología de la Facultad de Biología de la Universidad de Sevilla. 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 55 records from A revision of the New Zealand weevil genus Irenimus Pascoe, 1876 (Coleoptera: Curculionidae: Entiminae). 246 records from Rotifers of Macquarie Island. 6 records from New ants (Hymenoptera: Formicidae) from Micronesia. 4 records from A new anchialine species of Naushonia (Decapoda: Gebiidea: Laomediidae) from the Bahamas. 2 records from Schulgelände SGD/Viersen. 6 records from The genus Thelepus Leuckart, 1849 (Annelida, Thelepodidae) in Brazil, with a redescription of the holotype of T. setosus (Quatrefages, 1866). 2 records from A new diminutive sisorid catfish (Actinopterygii: Siluriformes) from northeastern India. 1 records from Rediscovery of Terebratulina austroamericana Zezina, 1981 (Brachiopoda: Cancellothyrididae) from off northern Chile. 42 records from Flies from L.A., The Sequel: A further twelve new species of Megaselia (Diptera: Phoridae) from the BioSCAN Project in Los Angeles (California, USA). 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 1306 records from Flora genérica de las gramíneas del estado de Tlaxcala. 11 records from Allopatric color forms of Scaphidium morimotoi Löbl, 1982 (Coleoptera, Staphylinidae, Scaphidiinae) endemic to the Amami Islands, the Ryukyus, Japan. 3 records from A new genus of Hemerobiidae (Neuroptera) from Baltic amber, with a critical review of the Cenozoic Megalomus - like taxa and remarks on the wing venation variability of the family. 1 records from Zur Kenntnis der Lithobiiden. 37 records from Revisionary systematics of the endemic soft coral fauna (Octocorallia: Alcyonacea: Alcyoniina) of the Agulhas Bioregion, South Africa. 15 records from Three species of Reteporella (Bryozoa: Cheilostomata) in a diapiric and mud volcano field of the Gulf of Cádiz, with the description of Reteporella victori n. sp. 2 records from A new species of Paraleptophlebia Lestage, 1917 (Ephemeroptera: Leptophlebiidae) and a re-description of adults for Paraleptophlebia westoni Imanishi, 1937 with the first description of the larva, from the Russian Far East. 2 records from Phasmarhabditis bonaquaense n. sp. (Nematoda: Rhabditidae), a new slug-parasitic nematode from the Czech Republic. 159 records from (Appendix C) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-967A. 2014 records from ZUEC-ARA - Coleção de Aracnideos do Museu de Zoologia da UNICAMP. 90243 records from PACA-AGP - Herbarium Anchieta. 35 records from The ant genus Tetraponera in the Afrotropical region: the T. grandidieri group (Hymenoptera: Formicidae).. 3 records from Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae). 22167 records from Natural History Museum Maastricht (NL) - Herbarium. 50 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. IV. Alopoglossidae, Gymnophthalmidae. 103 records from Invertebrate collections. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 10 records from Description of three new troglobiontic species of Cybaeodes (Araneae, Liocranidae) endemic to the Iberian Peninsula. 148 records from Other Arachnida collection of National Museum of Nature and Science. 17114 records from Collection of Coleoptera. 2 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 64 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 8853 records from Vascular Plants Collection of National Museum of Nature and Science. 12 records from A new species of Sextonia Chevreux, 1920 (Crustacea: Amphipoda: Liljeborgiidae) from the Okhotsk Sea. 4268 records from Free-living marine Nematodes from Ali, Rada Tilly and El Limite sandy beaches (Chubut, Argentina) 2006.. 17920 records from List of the specimens of the Vanuatu National Herbarium (PVNH). 8956 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 691 records from Barcant Butterfly Collection - Lycaenidae. 9 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 1 records from A new species of Silba (Diptera; Lonchaeidae) associated with figs. 29 records from Hypostomus velhochico, a new keeled Hypostomus Lacépède, 1803 (Siluriformes: Loricariidae) from the rio São Francisco basin in Brazil. 12 records from Description of a new catfish, Silurus tomodai (Siluriformes: Siluridae) from central Japan. 6 records from (Table 5) Paleotemperature estimates for DSDP Hole 81-552A. 31 records from Two new species of Eretmocerus Haldeman (Hymenoptera: Aphelinidae) parasitizing Aleurolobus rhododendri Takahashi and Dialeuropora decempunctata (Quaintance & Baker) (Hemiptera: Aleyrodidae) from Taiwan. 859118 records from Queensland Museum provider for OZCAM. 10267 records from Bruce Bennett Herbarium (BABY). 239 records from Fig. 7 (right) Macrofossil concentrations in core Lz1104-5. 25592 records from Herbarium Amazonense. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 229089 records from Vascular plant herbarium TRH, NTNU University Museum. 3587 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 6 records from A new genus of katydid from the Amazon Rainforest (Orthoptera: Tettigoniidae; Phaneropterinae; Steirodontini): Ninth contribution to the suprageneric organization of the Neotropical phaneropterines. 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 240 records from Chironomid remains in the sediment sequence of Site PG1212. 5316 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 3383 records from Lista florística de la Costa Grande del estado de Guerrero. 351 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 18 records from Two new fish species of the genus Puntius Hamilton (Cyprinidae) from Manipur, India, with notes on P. ticto (Hamilton) and P. stoliczkanus (Day).. 15 records from A new genus and four new species of subfamily Cyclocypridinae (Crustacea, Ostracoda) from Thailand. 2 records from Amtsrain Apolda-Zottelstedt. 4 records from A new species of Synotaxus and the first chromosomal study on Synotaxidae, presenting a rare XY sex chromosome system in spiders (Araneae, Araneoidea). 44 records from A review of the Callogobius (Teleostei: Gobiidae) from the Red Sea with the description of a new species. 3 records from A new species of the genus Gracixalus (Amphibia: Anura: Rhacophoridae) from Mount Jinggang, southeastern China. 8 records from Potamonautes nheenae, a new species of freshwater crab from Gabon, Central Africa, with a description of the first known male of Erimetopus brazzae (A. Milne-Edwards, 1886) from the Democratic Republic of the Congo, Central Africa (Brachyura: Potamoidea: Potamonautidae). 30 records from Descriptions of a new species and previously unknown males of Nesticus (Araneae: Nesticidae) from caves in Eastern North America, with comments on species rarity. 66116 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 36 records from A revision of the genus Medmassa Simon, 1887 (Araneae: Corinnidae) in the Afrotropical Region. 83 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 4 records from GEO-Hauptveranstaltung Bodden (Vilm). 18 records from The socially parasitic ant genus Strongylognathus Mayr in North Africa (Insecta: Hymenoptera: Formicidae).. 1 records from Nothrus pigerrimus. 4 records from Herpetology Collection. 230 records from Pilularia Globulifera distribution map in Denmark. 229708 records from UF FLMNH Ichthyology. 3 records from A new Antillobisium species (Arachnida: Pseudoscorpiones: Bochicidae) from Cuba, with biogeographical and ecological remarks on the genus. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 1698 records from Collection Paleoanthropology SMF. 13945 records from MfN - Fossil plants (Paleophytic). 2000 records from Mollusk Collection of Yokosuka City Museum. 1139 records from SWECO. 1694 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 2321 records from Dataset of fungus gnats (Diptera,Sciaroidea) from Møre og Romsdal county in Norway. 60101 records from EAC - Herbário Prisco Bezerra. 3 records from The male of the orb-weaving spider Plebs mitratus (Simon, 1895) and a redescription of the female (Araneae, Araneidae). 8006 records from Knerer collection / Gschwendtner property. 18542 records from DBG Sam Mitchel Herbarium of Fungi. 1 records from Description of a new neotropical species of Xiqilliba Kramer (Hemiptera: Cicadellidae: Neocoelidiinae). 30050 records from Collection Crustacea - ZMB. 2 records from Ceraphron krogmanni (Hymenoptera: Ceraphronidae), a new species from Lower Saxony with unusual male genitalia. 3 records from New data on the taxonomy, ecology, and conservation of the rediscovered Louisea edeaensis (Bott, 1969) (Brachyura: Potamoidea: Potamonautidae), an endangered freshwater crab from Cameroon. 60165 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 726 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 18 records from Peckoltia cavatica, a new loricariid catfish from Guyana and a redescription of P. braueri (Eigenmann 1912) (Siluriformes).. 1200 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 30 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 6 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 39190 records from Freshwater fishes of Poland. 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 2 records from The polyps of Oceania armata identified by DNA barcoding (Cnidaria, Hydrozoa). 4 records from On Starengovia Snegovaya, a genus of Asian nemastomatines (Arachnida: Opiliones: Nemastomatidae). 1 records from Myriopoden von Epirus. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 3 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 1399 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 154 records from Dermaptera in the icipe collection. 1 records from A new genus and species of Ingolfiellidae (Crustacea, Ingolfiellida) from the hyporheic zone in the Sierra de la Ventana, and its biogeographic relevance. 2344 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 33 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 14912 records from MVZ Egg and Nest Collection (Arctos). 1418 records from Fossil (GNHM-FO). 1002 records from Herbario HUAZ Enrique Forero. 6 records from Coendutermes tucum Fontes (Isoptera, Termitidae, Nasutitermitinae): description of the imago caste and additional notes. 16 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 2 records from Kabelskebach (Kabelsketal, Saalkreis). 2 records from Four new generic and 14 new specific synonymies in Pholcidae, and transfer of Pholcoides Roewer to Filistatidae (Araneae). 315 records from Naturalis Biodiversity Center (NL) - Orthopteroidea. 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 5 records from Gelände des IVL (Zeckern). 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 12 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 91739 records from E. C. Smith Herbarium (ACAD). 23238 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 80 records from Museu Paraense Emílio Goeldi - Platyhelminthes Collection. 173 records from Colección del Museo de Ciencias Naturales “José Lorca”. 1 records from EBCC Atlas of European Breeding Birds. 852 records from Estructura poblacional, variación genética y conservación de tres especies del género Pinus, endémicas de México. 72 records from Base de datos de Rana catesbeiana.. 5 records from Taxonomic revision of Saffron-billed Sparrow Arremon flavirostris Swainson, 1838 (Aves: Passerellidae) with comments on its holotype and type locality. 15 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 62 records from Uroptychus nitidus (A. Milne-Edwards, 1880) and related species (Crustacea: Decapoda: Anomura: Chirostylidae) from the western Atlantic. 1808 records from Consolidación y sistematización de las colecciones de referencia de peces y mamíferos marinos del ITESM Campus Guaymas. 111 records from The bees (Hymenoptera: Apoidea) of the Maltese Islands. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 1821 records from Inventario florístico de la Sierra de San Carlos, Tamaulipas. 5 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 10 records from Description of the larval stages of the Shield Darter, Percina peltata (Pisces: Percidae), in New York.. 836473 records from Museums Victoria provider for OZCAM. 6859 records from Plan de vertebrados de la Patagonia. 215195 records from SysTax - Zoological Collections. 9 records from Epimeria cleo sp. nov., a new crested amphipod from the Ross Sea, Antarctica, with notes on its phylogenetic affinities (Crustacea, Amphipoda, Eusiroidea, Epimeriidae). 2 records from A new amphibious troglobitic styloniscid from Brazil (Isopoda, Oniscidea, Synocheta). 2 records from A new species of the stenopodidean shrimp genus Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Ryukyu Islands, Indo-West Pacific. 4 records from Danielsberg (Mölltal, Kärnten). 1 records from A new species of nurse-frog (Aromobatidae, Allobates) from the Madeira River basin with a small geographic range. 71 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 877 records from Sphaeriid clams. 348 records from Updated list of bumblebees (Hymenoptera: Apidae) from the Spanish Pyrenees with notes on their decline and conservation status. 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 232661 records from Oklahoma Vascular Plants Database Provider. 350 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 11 records from Pteroceraphron Dessart new to the USA (Hymenoptera: Ceraphronoidea). 723716 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 740 records from Targeting a portion of central European spider diversity for permanent preservation. 187 records from UWIZM Mammals. 10907 records from Census of species recorded during phytosociological surveys in Benin. 2845 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 9 records from Oxynoemacheilus kentritensis, a new species from the upper Tigris drainage in Turkey with remarks on O. frenatus (Teleostei: Nemacheilidae). 16 records from A new species of Mesovelia (Heteroptera: Gerromorpha: Mesoveliidae) from South America, with identification key and notes on Colombian species. 6579 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 9 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 1240 records from Diversidad y conservación de orquídeas de la región de Chimalapa, Oaxaca, México. 36 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 6 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 50 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 9 records from Discovery of the genus Pseudepione Inoue, 1943 in Taiwan, with description of a new species (Lepidoptera: Geometridae: Ennominae). 6 records from On the new monotypic wolf spider genus Ovia gen. nov. (Araneae: Lycosidae, Lycosinae). 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 3933 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 2289 records from Specimen records of spiders (Arachnida: Araneae) by monthly census for 3 years in forest areas of Yakushima Island, Japan. 33 records from Relative abundance of Florisphaera profunda in ODP Hole 121-758C. 11 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 738 records from Correlación entre las condiciones ambientales y la pesquería de anchoveta a lo largo de la costa de Baja California. 6566 records from CABI Lepidoptera Collection. 4 records from Two remakable new species of Notocera Amyot and Serville, 1843 (Hemiptera, Membracidae, Hypsoprorini) from the Brazilian Caatinga. 124062 records from University of Guelph Insect Collection (DEBU). 2 records from Two new species of Sympagella (Porifera: Hexactinellida: Rossellidae) collected from the Clarion-Clipperton Zone, East Pacific. 19 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 2 records from Junge Heide, Radebeul/Dresden. 2 records from Naturgrundstück (Eutin). 809 records from ant-plant_symbioses. 28 records from Korean Plant Virus Database. 36 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 3 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 381 records from Coelenterata (Cnidaria and Ctenophora) collection of National Museum of Nature and Science. 30 records from New species of Hercostomus Loew, 1857 (Dolichopodidae, Diptera) from Japan. 29 records from Herbarium Senckenbergianum (FR) - Protista. 837 records from Colección de Zoología Invertebrados - Carcinología. 1 records from New earthworm records (Clitellata: Lumbricidae) from Bulgaria since 2012. 3 records from Zoology in the Middle East. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 3947 records from Herbario del Jardín Botánico-Histórico La Concepción: HBC. 7 records from Three new species of phytoseiid mites (Acari: Phytoseiidae) from Bahia State, Brazil. 159 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 6 records from Two new eriophyoid mite species (Trombidiformes: Eriophyoidea) from the cocoa tree, and a note on Shevtchenkella biseta (Nalepa). 21 records from Five new species of Stenochrus (Schizomida: Hubbardiidae) from Oaxaca, Mexico. 3367 records from Base de datos del Municipio General Heliodoro Castillo, Guerrero (120. Sierra Madre del Sur). 9 records from First record and new species of the Oriental leafhopper genus Trifida Thapa & Sohi (Hemiptera: Cicadellidae: Typhlocybinae) from China. 1354 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 651 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 28263 records from Collection Pisces SMF. 4 records from Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile. 7 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 35 records from Three new species of Mesovelia Mulsant & Rey (Hemiptera: Heteroptera: Mesoveliidae) from India. 8980 records from MEXU/Tipos de plantas vasculares. 32 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 1581 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 8 records from Macropsini (Hemiptera: Cicadellidae) of Thailand, with description of two new species and three new country records. 633 records from (Appendix A2) Relative abundances of benthic foraminifera and stable carbon isotope ratios of Nuttallides truempyi at the Paleocene-Eocene thermal maximum in ODP Hole 198-1210B in the central Pacific. 2029 records from Biodiversidad asociada a mantos de rodolitos y praderas de pastos marinos en Bahía Concepción, BCS. 26 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 2 records from Landschaftspflegehof (Berlin). 1 records from Bachpatenschaft Beeke. 13 records from First record of Africactenus Hyatt, 1954 and redescriptions of two poorly known species of Ctenus Walckenaer, 1805 (Araneae, Ctenidae, Cteninae) from India. 1 records from Parasitism of Hymenoepimecis manauara Pádua & Oliveira (Hymenoptera: Ichneumonidae: Pimplinae) on Leucauge henryi Mello-Leitão (Araneae: Tetragnathidae) in Brazilian Amazonian. 134 records from Review of Lecithoceridae (Lepidoptera: Gelechioidea) in the Oceanian Region, with description of a new species and a checklist of the family. 390 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 101 records from Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China. 1 records from The current status of Neocnus Arredondo, 1961 (Mammalia: Edentata: Pilosa: Megalonichidae) and a replacement name for its junior homonym in the sea cucumber family Cucumariidae (Echinodermata: Holothuroidea: Dendrochirotida: Cucumariidae). 2 records from Artenvielfalt auf den Elbwiesen (Dessau). 2 records from Two new species of Dactylonotus Parent, 1934 (Diptera: Dolichopodidae) from South Africa and a key to Afrotropical species. 6 records from Zanna robusticephalica sp. nov. (Hemiptera: Fulgoromorpha: Fulgoridae) from China, with comments on some ultrastructural characters of the new species. 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 194 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 38004 records from Vascular plants collection of Hiratsuka City Museum. 32 records from Description of two new species of Avicularia Lamarck 1818 and redescription of Avicularia diversipes (C. L. Koch 1842) (Araneae, Theraphosidae, Aviculariinae) - three possibly threatened Brazilian species. 3006 records from Plantas de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 20 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 386 records from Mammal specimens of Kawasaki Municipal Science Museum. 12 records from A new genus of nesticid spiders from western European Peninsulas (Araneae, Nesticidae). 47 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 836 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 3 records from Naturschutzgebiet Lochbusch-Königswiesen. 13 records from Visual Plants (144.41.33.158) - Private collection of Florian Werner. 73 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 1 records from Carabodes coriaceus. 7814 records from Odonata de Veracruz. 621 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 1 records from Two new species of earthworms belonging to the genus Amynthas (Oligochaeta: Megascolecidae) from Guangxi Province, China. 317 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Hole 115-714A. 330 records from The water striders (Hemiptera: Heteroptera: Gerridae) of Costa Rica: new species, checklist, and new records. 2695 records from UFRN-Fungos - Herbário UFRN - Fungos. 110558 records from Colección Herbario Federico Medem Bogotá - FMB. 37 records from A checklist of marine littoral mites (Acari) associated with mangroves. 1 records from Species of Macrostomum (Macrostomorpha: Macrostomidae) from the coastal region of Lima, Peru, with comments on M. rostratum Papi, 1951. 5 records from Three squat lobsters (Crustacea: Decapoda: Anomura) from tropical West Pacific seamounts, with description of a new species of Uroptychus Henderson, 1888. 33 records from New records of snail-killing flies (diptera: Sciomyzidae) from Iran. 144 records from Taxonomy of the South American genus Pachypops Gill 1861 (Teleostei: Perciformes: Sciaenidae), with the description of a new species.. 33 records from An annotated checklist of earthworms of Greece (Clitellata: Megadrili). 5 records from Two new species of the genus Leeonychiurus Sun & Arbea, 2014 (Collembola: Onychiuridae) from Korea. 3 records from Miriapodi cavernicoli del Marocco, della Sardegna e del Piemonte. 6393 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 2 records from A new species of Cales (Hymenoptera: Aphelinidae) parasitizing Bemisia pongamiae (Takahashi) (Hemiptera: Aleyrodidae) in Taiwan, with a key to world species of the Cales spenceri-group. 1379 records from Composition of the coccolith flora in sediment core GeoB1710-3. 1422 records from Reconocimiento de la biodiversidad de la Reserva de la Biósfera Calakmul: Odonata, psocóptera y díptera acuáticos (Insecta). 11 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 2 records from Faberpark (Nürnberg/Stein). 495 records from The South American spider genera Mesabolivar and Carapoia (Araneae, Pholcidae): new species and a framework for redrawing generic limits. 127 records from Collection Ephemeroptera - SMF. 894 records from (Appendix A3) Planktonic foraminifera of ODP Hole 166-1006A. 102476 records from Denver Museum of Nature & Science - Entomology. 3276500 records from Insecta of Costa Rica (INBio). 34829 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from A new Schistura from an upper Mekong affluent in Yunnan (Teleostei: Nemacheilidae). 35 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 162 records from Evaluación y monitoreo de manglar en la Reserva de la Biósfera Los Petenes con énfasis en criterios de sustentabilidad y desarrollo. 55 records from Revision of the soft scale genus Paralecanium (Hemiptera: Coccomorpha: Coccidae) with the introduction of three new genera and twenty new species. 74 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 15 records from Revision of the Chinese species of the genus Grouvellinus Champion, 1923 (Coleoptera: Elmidae). The G. acutus species group. 9000 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 7169 records from Collection of Hymenoptera. 4444 records from Actualización e incremento del banco de datos de la colección de herbario del Jardín Etnobotánico de Oaxaca. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 19 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 286 records from Berlin-Brandenburg Plant Collection 2006. 1351 records from (Appendix B) Relative abundances of larger size planktonic foraminifera in latest Maastrichtian sediments of DSDP Hole 74-525A from Walvis Ridge, South Atlantic. 10212 records from Spider (NSMK-SP). 31 records from Studies in Liocranidae (Araneae): redescriptions and transfers in Apostenus Westring and Brachyanillus Simon, as well as description of a new genus. 25173 records from OUPR - Herbário "Professor José Badini". 38 records from The Oriental species of the ant genus Probolomyrmex (Insecta: Hymenoptera: Formicidae: Proceratiinae).. 2 records from On several species of Oswaldella Stechow, 1919 (Cnidaria, Hydrozoa), including the description of a new species. 865 records from (Appendix A4) Planktonic foraminifera of ODP Hole 172-1062B. 1422 records from NZCS Invertebrates Old Collection Before 1987. 433 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 4 records from VFD-H: Heidenrod: Pferdeweide Mürth. 14339 records from Bird collection of National Museum of Nature and Science. 2 records from New distribution records for the rare genus Afrotremex Pasteels (Siricidae: Hymenoptera) and provision of interactive Lucid identification keys to species. 10650 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1 records from Resurrection of the earthworm species Dendrobaena fedtschenkoi (Michaelsen, 1900), a former synonym of Dendrobaena byblica (Rosa, 1893) (Clitellata: Megadrili). 18 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 1229 records from Insect Collection (CeStuBio). 5 records from First records of Dentridactylinae (Orthoptera: Tridactylidae) from Colombia, with description of two new species of Dentridactylus Günther. 2 records from A new species of Yllenus Simon, 1868 from northern India (Araneae, Salticidae). 1 records from Nottekanal, Klasse 7 - 10. 8 records from A new species of Hedya Hübner from Iran with proposed rearrangement of some species currently assigned to Metendothenia Diakonoff (Lepidoptera: Tortricidae). 5923 records from Australian Coral Ecoregions. 1 records from A new species of Ohilimia Strand, 1911 from New Guinea (Araneae: Salticidae). 2 records from An integrative description of Ramazzottius subanomalus (Biserov, 1985) (Tardigrada) from Poland. 12 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 11 records from The identity of the Carsidara species (Hemiptera: Psylloidea: Carsidaridae) associated with Firmiana simplex (Malvaceae) in Japan and Korea. 681 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Aves (MG-ZV-A). 2007 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 9 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 4221 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 7 records from Redescription and designation of a neotype for Ophiothrix angulata (Say, 1825) (Echinodermata: Ophiuroidea: Ophiotrichidae). 9276 records from (Appendix 3) Assemblage of benthic foraminifera in sediment core M5/2_KL15. 27 records from Sistemática molecular de Trogoniformes (Aves): Filogenia del orden y análisis de variabilidad genética de quetzales en la reserva de la Biosfera El Triunfo. 897332 records from MICROBIS database. 97349 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 9 records from The bark louse family Stenopsocidae (Psocodea: Psocomorpha) newly recorded from Laos, with description of three new species. 1 records from Zwei Flüsse - eine Stadt (Villingen-Schwenningen). 390 records from Aportación al conocimiento de la fauna de Ascidias del litoral Pacífico de México. 146 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 604 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 7 records from A new species of small and highly abbreviated caecilian (Gymnophiona: Indotyphlidae) from the Seychelles island of Praslin, and a recharacterization of Hypogeophis brevis Boulenger, 1911. 199556 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 6 records from Description of the Nymph of Tramea binotata (Rambur, 1842) (Odonata: Libellulidae). 59 records from (Fig. 2) Abundance of Uvigerina pygmaea in sediment core MD95-2040. 6197 records from Platynotina (Coleoptera: Tenebrionidae) collections on the World. 16 records from The Stenus cirrus group (Coleoptera, Staphylinidae) in Fujian, East China. 45 records from Seven new species of Loneura Navás (Insecta: Psocodea: ‘ Psocoptera’: Ptiloneuridae) from Valle del Cauca, Colombia. 4 records from A new troglobiotic Protaphorura (Collembola, Hexapoda) from the Siberia, Russia. 65411 records from Mammals Specimens. 2 records from Two new species of the genus Metaxonchium Coomans & Nair, 1975 (Nematoda, Dorylaimida, Belondiridae) from Vietnam. 1 records from First record of spongillaflies (Neuroptera: Sisyridae) from Colombia. 438 records from Lauri Mällo private collection of Lepidoptera. 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 3 records from Weidegut Rechab. 2 records from A new species and new record of Polycystididae (Rhabdocoela: Kalyptorhynchia) from China. 15000 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 1 records from Abcoronalis protrusus, a new paraboloponine genus and species (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) from Borneo. 107 records from Dichomeris Hübner, 1818 (Lepidoptera, Gelechiidae, Dichomeridinae) from Cambodia, including associated Chinese species. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 897 records from Trichoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 1 records from A new record of Potamanthellus caenoides Ulmer 1939 (Ephemeroptera: Neoephemereidae) from the southern Western Ghats of India. 8462 records from University Of Pretoria: Lacewing Database Project (1911-2015). 24 records from Paraorosius, a new genus of leafhopper (Hemiptera: Cicadellidae: Deltocephalinae: Opsiini), with description of a new species from the Middle East. 24 records from Perlesta armitagei n. sp. (Plecoptera: Perlidae): More cryptic diversity in darkly pigmented Perlesta from the eastern Nearctic. 4400 records from USAC Mammals Collection. 4299 records from New Zealand Biodiversity Recording Network. 3 records from A new species of the genus Colilodion Besuchet, 1991 (Coleoptera: Staphylinidae: Pselaphinae) from Mindanao, the Philippines. 20 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 218 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 3399 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 3 records from Description of the mature larva of Austrolimnius nyctelioides (Germain, 1892) and A. elatus Hinton, 1941 (Coleoptera: Elmidae). 1 records from The tenth member of stout newt (Amphibia: Salamandridae: Pachytriton): Description of a new species from Guangdong, southern China. 2603 records from Museu Paraense Emílio Goeldi - Paleoinvertebrate Collection. 7075 records from SMNS Herpetologie. 5 records from Redescription of a little-known spider species, Mesiotelus lubricus (Simon, 1880) (Aranei: Liocranidae) from China. 4 records from A new species of Ergasilus von Nordmann, 1832 (Copepoda: Cyclopoida) from the gills of a dasyatid ray, Himantura oxyrhyncha (Sauvage, 1878) from West Kalimantan, Indonesia. 93 records from The jumping plant-lice of the Neotropical genus Tainarys (Hemiptera: Psylloidea) associated with Anacardiaceae. 2068 records from Colección Zoológica de la Universidad del Tolima (CZUT)-Anfibios. 363 records from PSUZC-Reptile Collection. 61 records from Abundance of coccosphere-units of sediment core GIK23071-2. 82 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 42570 records from Bird Collection of Museum and Institute of Zoology PAS. 1513 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 2 records from Solving a nomenclatural conundrum: Cernosvitovia crainensis (Mršić, 1989) and Aporrectodea macvensis Šapkarev in Mršić, 1991 (Lumbricidae). 70 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 59 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 314 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 1 records from Lissotes working-group. 1 records from First columbellid species (Gastropoda: Buccinoidea) from deep-sea hydrothermal vents, discovered in Okinawa Trough, Japan. 6 records from Two new species of the genus Gibbotettix Zheng, 1992 (Orthoptera: Tetrigidae, Cladonotinae) from China. 14 records from Laophontodes typicus T. Scott (Copepoda, Harpacticoida, Laophontodinae) - discovering a species complex by morphology. 38 records from Visual Plants (144.41.33.158) - Plants from Costa Rica, illustrations by Teresa Barantes Lobo. 5635 records from Collection Echinodermata SMF. 45 records from Robert Forsyth Terrestrial Gastropods Collection. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 77414 records from MfN - Fossil vertebrates IV. 265 records from AIS Wildtype Populations of Arabidopsis. 10 records from Two new butterfly species (Lepidoptera: Rhopalocera) from Mount Cameroon, Gulf of Guinea Highlands, Cameroon. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 45168 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 3439 records from MEXU/Flora de Oaxaca. 6 records from Review of the genus Metopheltes Uchida, 1932 (Hymenoptera, Ichneumonidae) with description of a new species from Vietnam. 1 records from On the Chilopoda from Turkey. 124 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 4 records from A new species of the remarkable brittle star genus Astrophiura (Echinodermata: Ophiuroidea) from the western Atlantic Ocean. 1 records from A new species and a new record of Horaeomorphus Schaufuss (Staphylinidae: Scydmaeninae: Glandulariini) from China. 5 records from Description of a new Gibbaranea (Araneae: Araneidae) from the Western Mediterranean. 480 records from Sammlung Ernst Ule sinenumero Herbarium Hamburgense HBG. 5 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 1915 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 1387 records from Estudio de la diversidad florística de la región de Nizanda en el Istmo de Tehuantepec, Oaxaca. 9304 records from Echinoderm collection of National Museum of Nature and Science. 109176 records from Herps Specimens. 54 records from Ompok platyrhynchus, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 30535 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 57 records from Chromidotilapia melaniae and C. nana, two new cichlid species (Perciformes, Cichlidae) from Gabon, Central Africa.. 914939 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 64 records from Chenopodium vulvaria. 6 records from A new species of Stasimopus from the Eastern Cape Province of South Africa (Araneae, Mygalomorphae, Ctenizidae), with notes on its natural history. 3781 records from VMNH SVDM Vertebrate Paleontology. 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 16 records from The genus Ctenomelynthus (Hemiptera: Heteroptera: Coreidae: Acanthocephalini), with the description of three new species and key to the known species. 42 records from Contribution to the knowledge of the earthworm fauna of Turkey with description of three new species (Clitellata: Megadrili). 8 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 1 records from Description of a new species of the genus Mongolotettix Rehn, 1928 (Orthoptera: Acrididae) from Fujian, China. 150 records from Estudio de la variabilidad genética de Fundulus lima y sus relaciones filogeográficas con otros fundúlidos (Pisces: Fundulidae) de la Península de Baja California, México. 498 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 847 records from PAMP-tracheo: Vascular plants in La Demanda and Cameros mountain ranges (La Rioja, Spain). PhD project, L.M. Medrano. 4 records from Two new Afrotropical genera of Scatopsidae (Diptera). 3689 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 6638 records from Mammalia fossil Kleinsäuger - SMF. 6 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 1257 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-7. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 4 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 5 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 1 records from Arthropoden aus südostalpinen Höhlen.. 289 records from bmhs_butterfly_collection. 274 records from Herpetological Collection at the Wildlife Institute of India Vertebrate Museum. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 4 records from A new black fly species of Simulium (Simulium) (Diptera: Simuliidae) from Taiwan. 7 records from Vietelmis jablonskii, a new species of riffle beetle from Laos and Thailand and new faunistic records on Vietelmis Delève, 1968 from Malaysia (Coleoptera: Elmidae). 5710 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 37 records from Description of a new species of catshark, Atelomycterus marnkalha n. sp. (Carcharhiniformes: Scyliorhinidae) from north-east Australia.. 332 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 2 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 16 records from Revalidation of Acanthinozodium Denis, 1966 with description of three new species and discovery of a remarkable male palpal character (Araneae, Zodariidae). 43770 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 2 records from Description of two new idiocerine leafhoppers of the genus Chinaocerus (Hemiptera: Cicadellidae) from southwestern China. 1 records from Two new species of the subgenus Brachyphytodecta Bechyně, 1948 (Coleoptera, Chrysomelidae, Gonioctena) from Sichuan, Southwest China. 3 records from Hochschule Zittau/Görlitz. 36162 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 101 records from CNAN/Escorpiones Estado de Mexico. 22 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 439 records from Estado actual del conocimiento biológico de algunas especies de roedores de las familias Muridae, Geomyidae, Heteromyidae y Sciuridae (Rodentia: Mammalia) incluidas en el PROY-NOM-059-ECOL-2000. 36 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 6 records from Multivariate discrimination and description of a new species of Tapinoma from the Western United States.. 43 records from Three new species of the Encarsia inaron (Hymenoptera: Aphelinidae) species group from China with a key to Chinese species. 3 records from Undocumented beetle diversity in the Southeastern United States: a case study of the minute clubbed beetles (Coleoptera: Monotomidae). 3 records from Nationalpark Harz Schul-AG Braunlage. 4 records from Three species of Hydrobaenus Fries (Diptera: Chironomidae: Orthocladiinae) from Belarus. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 116417 records from Michigan State University Herbarium Lichens. 77 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 11 records from Thorectinae (Porifera: Demospongiae: Dictyoceratida) from Northeastern Brazil: two new species and transfer of Scalarispongia cincta (Boury-Esnault, 1973) to the genus Thorecta Lendenfeld, 1888. 199 records from Evaluación de la resistencia a la roya (Uromyces appendiculatus) en poblaciones silvestres y cultivadas de frijol, mediante el empleo de marcadores genéticos moleculares. 56 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto). 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 163 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 651 records from pbzt_insect_biodiversity. 35 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 52 records from Pelvicachromis signatus and Pelvicachromis rubrolabiatus, two new cichlid species (Teleostei, Perciformes) from Guinea, West Africa.. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 29137 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 41 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 156827 records from Wikiplantbase #Toscana. 2088 records from Publicación de la obra: American species of Acacia (Leguminosae; Mimosoideae). 228 records from Bishop's University Insect Collection (BUIC). 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 16 records from New data on cockroaches of the subfamily Epilamprinae (Dictyoptera: Blaberidae) from India and Sri Lanka, with descriptions of new species and the genital complex of Aptera fusca (Thunberg, 1784). 2972 records from Mammal collection NTNU University Museum. 9 records from New Oriental genera in the family Issidae (Hemiptera: Fulgoromorpha). 132007 records from BioFokus. 11 records from Glossing over cryptic species: Descriptions of four new species of Glossodoris and three new species of Doriprismatica (Nudibranchia: Chromodorididae). 6 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 228 records from An annotated checklist of the Chilopoda and Diplopoda (Myriapoda) of the Abrau Peninsula, northwestern Caucasus, Russia. 376 records from Códigos de barras de helmintos de anfibios y reptiles de México. 115365 records from TTU Mammals Collection. 71494 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 47 records from New species and additional data on the chewing louse genus Myrsidea (Phthiraptera: Menoponidae) from wild Neotropical Passeriformes (Aves). 1824 records from CNAN/Scorpiones. 104 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 3 records from Aplectana nordestina n. sp. (Nematoda: Cosmocercidae) parasitizing Leposternon polystegum (Squamata: Amphisbaenidae) from Northeastern, Brazil. 8649 records from Fossil (WSHN-FO). 4 records from A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China. 1 records from A new species of Hemidactylus (Squamata: Gekkota: Gekkonidae) from Qara Dagh Mountains, Kurdistan Region, with a key to the genus in Iraq. 4 records from Two new genera and species of the leafhopper tribe Idiocerini (Hemiptera: Cicadellidae) and redescription of the type species of Paraidioscopus. 357 records from bmhswatsonshellcollection. 7 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 2775 records from CeDoc de Biodiversitat Vegetal: BCN- Algues de J. Rodríguez Femenías. 13 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 33 records from Taxonomic revision of the Neotropical genus Caenopangonia Kröber, 1930 (Diptera: Tabanidae). 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 8 records from A new species of Orthosiphon (Lamiaceae) from Angola. 5 records from Persianorchestia, a new talitrid genus (Crustacea: Amphipoda: Talitridae) from Gulf of Oman, Iran. 425 records from Collection de C.C.H. Jongkind aux Monts Nimba (BID-AF2015-0066-REG). 4 records from Yunnanosticta gen. nov., from Yunnan, a new genus from the Sinostictinae, with the description of two new species (Odonata: Zygoptera: Platystictidae). 2443 records from Cnidaria MZS. 26 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 7351 records from Museu de Ciències Naturals de Barcelona: MCNB-Pal. 13 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 14 records from Laetosphecia, a new genus of clearwing moths from south-eastern China, with a brief review of the Sesiini from China (Lepidoptera, Sesiidae). 8 records from A review of the ant genus Metapone Forel from Madagascar.. 30 records from bmhs_echinoderm_collection. 6 records from Mammalia (JNHM-MM). 18 records from Alpheus luiszapatai, a new species of rare and colorful deep water alpheid shrimp (Crustacea: Decapoda: Alpheidae) from Arusí, Chocó Department, Pacific Coast of Colombia. 115 records from On the absence of the Green-tailed Trainbearer Lesbia nuna (Trochilidae) from Venezuela: an analysis based on environmental niche modelling. 713 records from (Appendix 4) Stable oxygen isotope record of Globigerina bulloides and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2040. 10 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 13940 records from The Vascular Plants Collection of the University of Goettingen. 2120 records from Flora vascular acuática de la cuenca del Río Tamesí. 8 records from A revision of the genus Lepidobrya Womersley (Collembola: Entomobryidae) based on morphology and sequence data of the genotype. 59 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 42 records from New species and records of Perlidae (Plecoptera) from Espírito Santo State, Brazil. 401 records from A review of the North American species of the fungus-gardening ant genus Trachymyrmex (Hymenoptera: Formicidae).. 5664 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 348 records from Inventario Nacional de Candelilla (Euphorbia antisyphilitica) Fase I.. 55 records from A taxonomic revision of the Pheidole roosevelti-group (Hymenoptera: Formicidae) in Fiji.. 5 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 732 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 9 records from New data on brown lacewing genus Wesmaelius Krüger, 1922 from China (Neuroptera, Hemerobiidae), with a key to Chinese species. 5327 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 10509 records from Andes to Amazon Biodiversity Program. 182790 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 665 records from Collection Echinodermata - ZMB. 28 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 17 records from Two new species of armoured spiders from Vietnam and Cambodia (Araneae: Tetrablemmidae: Pacullinae). 1 records from WildesMoor bei Schwabstedt. 443 records from Inventario herpetofaunístico del noroeste de Hidalgo. 3559 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 3 records from Three new species of jumping spiders of the genus Hypaeus Simon, 1900 from Colombia (Salticidae: Salticinae: Amycini). 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 7 records from Revision of the genus Hormoserphus Townes, 1981 (Hymenoptera: Proctotrupidae), with description of Trachyserphus gen. n. and a new species. 12 records from Update of the genus Leptochiton (Mollusca: Polyplacophora) in Chilean deep waters: three new reports and description of two new species. 511 records from Plantas del municipio El Carmen de Chucurí, Santander - Proyecto Santander BIO. 268 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 234 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 41984 records from Repatriación de datos de los lepidópteros depositados en la Colección del McGuire Center for Lepidoptera and Biodiversity, Florida Museum of Natural History. 13 records from Aves de fragmentos de Bosque seco en la región del Caribe Colombiano. 4 records from Studies on Dendrothripinae (Thysanoptera, Thripidae) from Japan, with new records and one new species. 11 records from Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae). 2326 records from Jardín Botánico Atlántico, Gijón: JBAG. 7320 records from Aves Collection of Institute of Systematics and Evolution of Animals. 7829 records from Universidad Autónoma de Madrid, Biología, Acalypha. 1 records from Description of a new species of the Ponerine ant genus, Emeyopone (Hymenoptera: Formicidae) from Karnataka, India.. 2225 records from Abundances of organic-walled dinoflagellate cysts in sediment core GeoB5546-2. 6238 records from Herbarium specimens of CBNA (GAP). 6242 records from Natural history museum data on Canadian Arctic marine benthos. 1137 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 1 records from A new species of Rock Gecko of the genus Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from Belitung Island, Indonesia. 7 records from Three new species of Epigomphus (Odonata: Gomphidae) from Costa Rica. 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 2989 records from Sponge collection of National Museum of Nature and Science. 20 records from Two new species of Curculionichthys (Siluriformes: Loricariidae) from the rio Amazonas basin, Brazil. 607 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 7638 records from Crustaceos del Museo de Ciencias naturales de la Universidad Simón Bolívar. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 373028 records from South Australian Museum Australia provider for OZCAM. 1 records from A new species of Tapiena (Orthoptera: Tettigonioidea: Phaneropterinae) from Brunei Darussalam (Borneo, Southeast Asia). 25 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 1261 records from MGC Herbarium of University of Malaga (Spain): MGC-Briof dataset. 100 records from Brock University Herbarium (BU). 148 records from Herbarium BSG Hepaticopsida. 10 records from Arachnid specimens of Okinawa Prefectural Museum & Art Museum. 214 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1246-4. 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 16138 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Cryptogamic National Collection (BAc). 26 records from Five species of the genus Epicephala Meyrick, 1880 (Lepidoptera: Gracillariidae) from China. 1040 records from Invasive Alien plant species of Malawi. 309 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 4 records from Redescription of Alopecosa albostriata (Araneae: Lycosidae) based on specimens from Siberia. 5 records from A description of three new species of the genus Alienia Fibiger, 2011 from Southeast Asia (Lepidoptera, Erebidae, Hypenodinae: Micronoctuini). 22 records from Genetic and morphological evidence for a new cryptic species of Ectinogonia (Coleoptera: Buprestidae) from central Chile. 38 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 28 records from Checklist of the freshwater snails (Mollusca: Gastropoda) of Mongolia. 86 records from UWIZM Cnidarians. 2039 records from Collections de coquilles continentales du Muséum d'histoire naturelle de Grenoble. 836 records from Visual Plants (144.41.33.158) - Botanical garden, University of Hohenheim, Germany. 6491 records from Les Rubiaceae, Orchidaceae, Moraceae, Sapindaceae, Malvaceae, Melastomataceae, Verbenaceae, Loganiaceae, Sapotaceae, Scrophulariaceae, Sterculiaceae, Liliaceae, Meliaceae, Ochnaceae, Tiliaceae, Rosaceae, Solanaceae, Violaceae, Zingiberaceae, Myrtaceae, Rutaceae, Loranthaceae et quelques 71 autres familles de plantes de l'Herbier du Centre National de Floristique en Côte d'Ivoire.. 119 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 1059 records from irregularia_mexico. 5 records from Troglocaris (Xiphocaridinella) kumistavi sp. nov., a new species of stygobiotic atyid shrimp (Crustacea: Decapoda: Atyidae) from Kumistavi Cave, Imereti, Western Georgia, Caucasus. 3 records from Cylindroniscus platoi (Isopoda: Oniscidea: Styloniscidae), a new cave-dwelling species from Lagoa Santa Karst, Southeastern Brazil. 280 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 372 records from Colección de Entomología - Arthropoda. 152102 records from Tasmanian Museum and Art Gallery provider for OZCAM. 40153 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 968 records from TTRS Mammals. 9 records from Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar. 35 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 132 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Fósseis (ZUFMS-FOS). 887 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 21235 records from Fish specimens of Bihoro Museum. 462 records from Collection Lepidoptera SMF. 95 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2 records from Mormolyce matejmiciaki sp. nov. (Coleoptera: Carabidae: Lebiinae) from Borneo. 99749 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 1 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 1 records from Description of a new Kempnyia Klapálek from Brazil (Plecoptera: Perlidae) with life stages associated using DNA barcodes. 64 records from Review of Poecilimon species with inflated pronotum: description of four new taxa within an acoustically diverse group. 6 records from New Galumnoidea (Acari, Oribatida) from Hanoi (Northern Vietnam). 1140 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 28 records from The Apseudomorpha (Crustacea: Tanaidacea) of the Gulf of Cadiz and Horseshoe Continental Rise (NE Atlantic): A taxonomic review with new records, species, and ecological data. 3 records from On two Italian Lithobius species described by Silvestri, with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda, Lithobiida). 1 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 41 records from Registros Primates Neotropicales Convocatoria APC. 19 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 760 records from Arthropoda specimens of Toyama Science Museum. 973 records from Spectacled bear database for Peru. 4 records from Two new species of Atlantoscia Ferrara & Taiti, 1981 (Isopoda: Oniscidea: Philosciidae) from southern Brazil described in the light of integrative taxonomy. 1 records from Hoplophora ardua. 43 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna”. 11 records from Two new species of the genus Atractoscion, and resurrection of the species Atractoscion atelodus (Günther 1867) (Perciformes: Sciaenidae). 1231 records from Benthic foraminifera of sediment core M25/4-KL13. 4 records from Flightless Catapionus (Coleoptera: Curculionidae: Entiminae) in Southwest China survive the Holocene trapped on mountaintops: new species, unknown phylogeny and clogging taxonomy. 150 records from Collection des données de biodiversité marine de Polynésie française - IRD Nouvelle-Calédonie. 5 records from Description of female of Titidius urucu Esmerio & Lise, 1996 (Araneae: Thomisidae). 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 14 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 7128 records from La familia Asclepiadaceae en México. 18 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 17 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 1 records from On two new synonyms of the orb-weaving spider Orsinome vethi (Hasselt, 1882) (Araneae, Tetragnathidae). 4 records from New species of Raphidascaris (Sprentascaris) (Nematoda: Anisakidae) in Rineloricaria steinbachi (Actinopterygii: Loricariidae) from Northwest Argentina. 34 records from Morphological examination and phylogenetic analysis clarify the taxonomic status of Cuban Longior Travassos & Kloss, 1958 (Nematoda: Thelastomatoidea: Hystrignathidae). 4 records from A new carpenter ant, Camponotus parabarbatus (Hymenoptera: Formicidae) from India. 178 records from Sediment components of core SO82-4. 5 records from One new Pseudopoda species group (Araneae: Sparassidae) from Yunnan Province, China, with description of three new species. 3 records from Lindau im Bodensee. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 112603 records from Herbarium Willing. 2114 records from Hongos ectomicorrizógenos y myxomycetes asociados con Picea chihuahuana en la Sierra Tarahumara. 46933 records from Botanical Museum, Copenhagen, Mycology Herbarium. 1716 records from KTU Pinophyta. 17713 records from NCSM Mammals Collection. 100 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 4 records from A new species of Selatosomus Stephens and the occurrence of Pristilophus melancholicus (Fabricius) in China (Coleoptera: Elateridae: Dendrometrinae). 1 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 7 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 28 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Pycnogonida.. 20027 records from Coleção de Porifera do Museu Nacional - UFRJ. 76262 records from Colección de Entomología del Instituto Alexander von Humboldt. 158 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 57 records from The subspecific structure of Dorcadion (Cribridorcadion) pusillum Küster (Coleoptera: Cerambycidae) with description of two new subspecies from Romania. 4 records from Two new cavernicolous Pselaphinae (Coleoptera: Staphylinidae) from southern China. 1 records from On the Chilopoda from Turkey. 7848 records from Insect specimens of Toyota City Nature Sanctuary. 4207 records from CASES2003_2004. 6 records from Taxonomy and biology of Simulium clarkei Stone & Snoddy (Diptera: Simuliidae), a poorly known black fly of the southeastern United States. 124 records from North Marine Region whaler shark collection records (DEW collation), Australia (1999- 2005). 3 records from Nouvelles fourmis de Madagascar.. 376 records from Digitalización y sistematización de las colecciones biológicas del INECOL. 570 records from Flora ficológica marina de Tamaulipas. 151 records from CHAS Botany Collection (Arctos). 1 records from A new species of Sweltsa (Plecoptera: Chloroperlidae) from Sichuan Province of southwestern China. 2 records from New ichneumonids (Hymenoptera, Ichneumonidae) from the Eocene Tadushi Formation, Russian Far East. 172074 records from CONN. 44267 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 12 records from Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand. 12289 records from ISM Mammalogy Collection. 34276 records from The avian collection at the Natural History Museum, Oslo, Norway. 374 records from Medicinal potential of African plants (Togo). 91 records from Phytoseiid mites (Acari: Phytoseiidae) associated with tropical ornamental plants, with a checklist and a key to the species of Bahia, Brazil. 8330 records from Nijmegen Natural History Museum (NL) - Herbarium. 3 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 39 records from Nothocasis rosariae sp. n., a new sylvicolous, montane species from southern Europe (Lepidoptera: Geometridae, Larentiinae). 2 records from Studies in Guatemalan Ensifera: Mayacephalus (Orthoptera: Tettigoniidae) a new cone-headed katydid genus. 282 records from MfN - Fossil invertebrates IIa. 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Ceará State) and Sete Cidades (Piauí State) National Parks, Northeastern Brazil. 1 records from Omoleon jeanneli, new record from Kenya and a redescription (Neuroptera: Myrmeleontidae). 8 records from Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India. 251 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 12939 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 92400 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 203 records from Occurrence datasets of Freshwater Snails (Gastropoda) of Kenya mobilized from the Zoological Collection of National Museums of Kenya, Nairobi and Literature. 4837 records from Free-living marine Nematodes from San Antonio and Cormoranes sandy beaches (Rio Negro, Argentina), 2006.. 6 records from A revision of Holothuria (Halodeima) kefersteinii (Selenka, 1867) and the revival of Holothuria inornata Semper, 1868 from sea cucumbers collected in Mexico and Central America. 1 records from Zetes lucorum. 1012 records from Collection Arachnida - ZSRO. 4745 records from Collection botanique Le Grand A. (BOUM). 26642 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv). 37 records from Cyanobacteria of Algal Collection of Soil Science Institute (ACSSI). 7032 records from FBIP: Systematics of South African Hymenoptera. 30 records from Lacantunia enigmatica (Teleostei: Siluriformes) a new and phylogenetically puzzling freshwater fish from Mesoamerica.. 7 records from ZUEC-BRA - Coleção de Brachiopoda do Museu de Zoologia da UNICAMP. 5 records from Description of the male of Phoebe ornator (Tippmann, 1960) (Coleoptera: Cerambycidae: Lamiinae: Hemilophini), analysis of the species biogeography, and first observation of chromatic gender dimorphism in Hemilophini. 78 records from Geographical and bathymetric distribution of mysids (Crustacea: Mysida) in the seas of the Iberian Peninsula. 50 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 5 records from New species and synonymy in the genus Corotoca Schiødte, 1853 (Coleoptera, Aleocharinae, Corotocini). 12 records from Integrative taxonomy of Hemimycale (Hymedesmiidae: Poecilosclerida: Demospongiae) from Southeastern Brazil, with the description of two new species. 1 records from Flusswerder in der Weser (Hameln). 15 records from Description of a new species of Caridina (Crustacea: Decapoda: Atyidae) from two Micronesian islands (Guam and Babeldaob). 1 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 29002 records from Computarización de la Colección Nacional de insectos Dr. Alfredo Barrera Marín del Museo de Historia Natural de la Ciudad de México. 11 records from On The Relationships of the Spider Genus Cybaeodes (Araneae, Dionycha). 3 records from Unraveling a new lineage of Hydrobiidae genera (Caenogastropoda: Truncatelloidea) from the Ponto-Caspian region. 39 records from Navigator, a new endemic genus of Cetoniinae (Coleoptera: Scarabaeidae) from Australia, with descriptions of two new species and behavioural studies. 28 records from A new endemic species of Willowsia from Florida (USA) and descriptive notes on all New World Willowsia (Collembola: Entomobryidae). 3 records from The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae). 2 records from The discovery of Euryrhynchidae (Crustacea: Decapoda) in India, with the description of a new genus and species. 8 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 702 records from Factual Database of Native Flora Seeds in Korea. 3974 records from DBL_Life. 4 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 238 records from Seven new species of Spathidexia Townsend (Diptera: Tachinidae) reared from caterpillars in Area de Conservación Guanacaste, Costa Rica. 424 records from The types of Phasmida in the Natural History Museum, London, UK. 9 records from Taxonomy of Oceanapia Norman, 1869 (Demospongiae: Haplosclerida: Phloeodictyidae) from the Brazilian coast. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 1534 records from PonTaurus collection. 859 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 4 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 20414 records from Auckland Museum NZ Marine Collection. 95 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 6 records from Systematic account of new Porifera (Demospongiae) records from the oceanic Island of Madeira (NE Atlantic). 2105 records from Acari Collection - Instituto Nacional de Pesquisas da Amazônia. 2479 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 2 records from A new skate genus Orbiraja (Rajiformes: Rajidae) from the Indo-West Pacific. 1 records from Description of Tottonophyes enigmatica gen. nov., sp. nov. (Hydrozoa, Siphonophora, Calycophorae), with a reappraisal of the function and homology of nectophoral canals. 213 records from Fig. 7. Relative abundance of ostracod species in composite core JH05. 2 records from One new species of the genus Xizicus (Orthoptera: Tettigoniidae: Meconematinae) from Chongqing, China. 4 records from Two new species of cave-dwelling Charinus Simon, 1892 from Brazil (Arachnida: Amblypygi: Charinidae). 2 records from Deux nouvelles espèces d’ Aloe L. (Xanthorrhoeaceae, Asphodelaceae), section Lomatophyllum Rowley, de Madagascar. 613 records from Implementación de la bioindicación en el Río Cauca - 2016. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 104 records from BID-Malawi-Arctiidae-Biodiversity-Data. 7074 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 39 records from The genus Acellomyia González, a new taxonomic arrangement of its species and descriptions of a new genus and two new species from southern South America (Diptera: Tabanidae: Diachlorini). 89 records from Bird specimens of Ryukyu University Museum (Fujukan). 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulidées d'Europe. 23 records from UWIZM Turtles and Crocodilians. 2 records from A new species of Eupariini from Eocene Baltic amber (Coleoptera: Scarabaeidae: Aphodiinae). 731 records from An updated record of Gaden Robinson's collection of Macro-moths of Fiji and Rotuma. 103 records from Studies on neotropical Phasmatodea XVII: Revision of Phantasca Redtenbacher, 1906, with the descriptions of six new species (Phasmatodea: Diapheromeridae: Diapheromerinae). 7 records from The taxonomic and phylogenetic status of some poorly known Anolis species from the Andes of Colombia with the description of a nomen nudum taxon. 7 records from Sangpradubina, an astonishing new mayfly genus from Thailand (Ephemeroptera: Leptophlebiidae: Atalophlebiinae). 3 records from A new species of Caligus Müller, 1785 (Copepoda: Siphonostomatoida: Caligidae) from coral reef plankton in the Mexican Caribbean. 171 records from Hormigas de hojarasca asociadas a fragmentos de bosque y cafetales de la zona cafetera de Cundinamarca. 1764 records from Arachnida of Costa Rica (INBio). 3 records from Two new Cambodian semi-aquatic earthworms in the genus Glyphidrilus Horst, 1889 (Oligochaeta, Almidae), based on morphological and molecular data. 53 records from Neotype designation for Sphingius thecatus Thorell, 1890, synonymies, new records and descriptions of six new species from Southeast Asia (Araneae, Liocranidae). 3148 records from Ross A. Layberry, Collection. 94 records from Collection Reptilia fossil SMF. 20 records from The Pinnotheridae of the northeastern Pacific (Alaska to Mexico): zoogeographical remarks and new bivalve hosts (Crustacea, Brachyura, Pinnotheridae). 3 records from Tardigrada and Rotifera from moss microhabitats on a disappearing Ugandan glacier, with the description of a new species of water bear. 1942 records from Western Australia Museum, Marine Invertebrate Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1952-2004. 24 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 15902 records from Field Museum of Natural History (Botany) - Historical Photographs of Type Specimens from Berlin (B). 1 records from Alloionema californicum n. sp. (Nematoda: Alloionematidae): a new alloionematid from USA. 2 records from Anaxibia folia spec. nov. - a new litter-dwelling dictynid spider from India (Araneae: Dictynidae: Dictyninae). 54 records from The Jordan theropod (Maastrichtian, Montana, U. S. A.) referred to the genus Aublysodon.. 3 records from Barsine deliciosa, a new species from China (Lepidoptera, Erebidae, Arctiinae). 8 records from Coralliidae (Anthozoa: Octocorallia) from the INDEMARES 2010 expedition to north and northwest Spain (northeast Atlantic), with delimitation of a new species using both morphological and molecular approaches. 82933 records from Herbario Amazónico Colombiano. 2 records from Papakula and Hesydrimorpha: how two spider genera were described from the same species collected from the same locality (Araneae: Pisauridae). 2 records from Discovery of the subfamily Rhopalomutillinae (Hymenoptera: Mutillidae) in China and description of Pherotilla brothersi sp. nov.. 1825 records from Galathea II, Danish Deep Sea Expedition 1950-52. 12497 records from NCSM Non-molluscan Invertebrates Collection. 2400 records from Flora y datos básicos para la evaluación de las actividades apícola y forestal en tres áreas focales del corredor Sian Ka'an-Calakmul. 111529 records from The AAU Herbarium Database. 31 records from (Appendix 1) DSDP Site 94-607A ostracode species census data. 306 records from Diversidad y distribución de las comunidades de fitoplancton y peces de ríos y lagunas del volcán San Martín de la reserva de la biósfera Los Tuxtlas. 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 1 records from Murcia ephippiata. 5810 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 6 records from Two new species of deeper dwelling Apogon (Perciformes: Apogonidae) from Micronesia and South Pacific Ocean.. 8 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 21 records from New and remarkable leafhoppers and planthoppers (Hemiptera: Auchenorrhyncha) from Switzerland. 1483 records from Sistematización de la Colección Entomológica Forestal del CENID-COMEF. 451 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 834 records from Database about reference specimens for medicinal plants, in the Apocynaceae family, owned by CNARP. 4375 records from Colecção Entomológica do Museu de História Natural de Maputo. 210017 records from Invert Paleo Specimens. 5 records from Neoclita pringlei (Scarabaeidae, Cetoniinae), a new relict genus and species from the Drakensberg Range of South Africa. 1 records from A new species of the phyline plant bug genus Chimairacoris from central Sulawesi, Indonesia (Hemiptera: Heteroptera: Miridae: Phylinae). 6 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 128 records from Coleção de Nematoda do Museu Nacional - UFRJ. 14502 records from Lepidoptera (Rhopalocera y Heterocera) de áreas prioritarias para la conservación en la Península de Yucatán, con registros de adultos y estados inmaduros. 8 records from A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia. 31082 records from MEXU/Plantas Vasculares. 9 records from One new species of the genus Acosmetura and supplement of Acosmetura emeica Liu & Zhou, 2007 (Tettigoniidae: Meconematinae) from Sichuan, China. 2416 records from Inventario de macroalgas de Bahía de Banderas: Fase I y Fase II. 284292 records from University of Michigan Museum of Zoology, Division of Insects. 1 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 3 records from A remarkable new species of the genus Lepisiota Santschi (Hymenoptera: Formicidae) from Oman and the United Arab Emirates with a key to the Arabian species. 15 records from Three new species of Entomobrya from Poland (Collembola, Entomobryidae). 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 4 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 7 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 11249 records from Heteroptera collections of SW Finland. 40 records from Additions to the knowledge of the land snails of Sabah (Malaysia, Borneo), including 48 new species. 2 records from First description of the last instar larva and pupa of the aquatic crane fly Limnorimarga limonioides (Alexander, 1945) (Diptera: Limoniidae). 2740 records from Fungi specimens of Saitama Museum of Natural History. 29844 records from Collection Ichthyologie - SNSD. 6722 records from Actualización de la base de datos del Herbario de la Universidad de Sonora (USON). 1129 records from Mollusca Collection of Saitama Museum of Natural History. 3 records from Taxonomy and Natural History of Strumigenys thaxteri Wheeler and Strumigenys reticeps (Kempf) (Hymenoptera: Formicidae). 921 records from Distribution of aquatic beetles from the east of Morocco (Coleoptera, Polyphaga). 1 records from Oribates fusifer. 4 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 4 records from A new species of Ninia (Serpentes: Dipsadidae) from Chocó-Magdalena biogeographical province, western Colombia. 630 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 378 records from (Appendix A) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene desiments of DSDP Hole 94-607 from the North Atlantic. 45070 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Herpetology National Collection (MACNHe). 6039 records from Plantas de La Frontera (ecorregión 12.1.1.1), e inventario florístico del Rancho El Aribabi, municipio de Imuris, Sonora. 29 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 11224 records from Fungi collection of Jyväskylä University Museum. 61 records from Nemertini - SMF. 1187 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase II (Tlahuelompa y Eloxochitlán). 5 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 4 records from A new canopy-dwelling species of Dendrelaphis (Serpentes: Colubridae) from Sinharaja, World Heritage Site, Sri Lanka. 46680 records from Bosque Mesófilo de Montaña de México. 662353 records from NMNH Paleobiology Specimen Records. 57 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 18 records from Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China. 52194 records from DMNS Bird Collection (Arctos). 2 records from Amphibian specimens of Obihiro Centennial City Museum. 16 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 3 records from A new species and key to all known species of the genus Filchnerella Karny, 1908 from China (Orthoptera: Acridoidea, Pamphagidae). 1004 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 119842 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 3 records from Australian Formicidae.. 5410 records from Collection ornithologique A. Maës. 31 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 5 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 89 records from Mammal specimens of Komatsu City Museum. 1 records from Ophichthus johnmccoskeri sp. nov. (Anguilliformes: Ophichthidae): a new snake eel from Indian waters, Bay of Bengal. 21 records from New species of Narberdia Burke from México and Central America (Coleoptera: Curculionidae). 547 records from RMT Trawl catch from the 2005/06 V3 BROKE-West voyage - Fish. 8564 records from Bird specimens of Himeji City Science Museum. 281886 records from Naturalis Biodiversity Center (NL) - Aves. 609 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 3 records from Dispatch from the field II: the mystery of the red and blue Opadometa male (Araneae, Tetragnathidae, Opadometa sarawakensis). 21 records from Hungarosoma bokori Verhoeff, 1928 (Diplopoda: Chordeumatida): new insights into its taxonomy, systematics, molecular genetics, biogeography and ecology. 31 records from A review of Labidostomis species similar to L. longimana from southeastern Europe with descriptions of two new species from Greece and Turkey (Coleoptera: Chrysomelidae: Cryptocephalinae: Clytrini). 1490 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 4634 records from University of Manitoba (WIN) - Lichen Collection. 10 records from Larvae of three East-Asian species of Nemoura (Plecoptera: Nemouridae). 1 records from A new genus and species of bark mantis from Thailand, with an updated key to the bark mantis genera of the Oriental region (Insecta: Mantodea). 4071 records from CSIC-Real Jardín Botánico-Colección de Hepáticas (MA-Hepat). 1 records from A new species of Enoplomischus from Kenya (Araneae: Salticidae: Leptorchestinae). 27194 records from Natural History Museum Rotterdam (NL) - Chordata collection. 284 records from Localities for the arachnid genus Acuclavella (Opiliones, Ceratolasmatidae). 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 6 records from Revision of the leafhopper genus Gurawa (Cicadellidae: Deltocephalinae: Chiasmini) from Pakistan with description of a new species. 406575 records from Herbarium of Taiwan Forestry Research Institute. 3698 records from NIWA Invertebrate Type Collection. 5 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 180 records from Down-core abundances of Turborotalia quinqueloba and Globorotalia inflata of sediment core GeoB5546-2. 7066 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 292 records from Gymnotus ucamara: a new species of Neotropical electric fish from the Peruvian Amazon (Ostariophysi: Gymnotidae), with notes on ecology and electric organ discharges.. 258 records from Malawi-Histeridae-Biodiversity-Data. 538 records from Recent noteworthy findings of fungus gnats from Finland and northwestern Russia (Diptera: Ditomyiidae, Keroplatidae, Bolitophilidae and Mycetophilidae). 2149 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 1540 records from (Appendix A) Relative abundance of planktonic foraminifera in ODP Hole 117-723A. 25374 records from Collections of Phytoplankton at BGBM. 5 records from First record of Pulvinaria urbicola Cockerell (Hemiptera: Coccidae) from India, with a key to the Indian species of Pulvinaria Targioni Tozzetti. 8 records from Contribution to the knowledge on the spider wasps genus Morochares Banks, 1934 (Hymenoptera: Pompilidae) from China. 10 records from A new burrowing crayfish of the genus Fallicambarus Hobbs, 1969 (Decapoda: Cambaridae) from the Red River Drainage of the southcentral United States. 1 records from Schistura alboguttata, a new loach species of the family Nemacheilidae (Pisces: Cypriniformes) from the Pearl River basin in Guangxi, South China. 3 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 1 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 4 records from Replacement names for two homonyms of Liothrips brevitubus Karny: one from California, the other for a species damaging Jatropha crops in Mexico. 15823 records from Naturalis Biodiversity Center (NL) - Echinodermata. 1 records from Oribates calcaratus. 115 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 471003 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1000 records from Axel W. Erikssons African Bird Collection at Vänersborg Museum. 5335 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 1882 records from Carabidae of the European North-East of Russia. 4019 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 403 records from Revision of Afrotropical Dyscritobaeus Perkins, 1910 (Hymenoptera: Scelionidae). 2 records from A new species of the genus Ancylocheles Haig, 1978 (Crustacea: Decapoda: Anomura: Porcellanidae) from Gujarat, northwestern India. 11941 records from Universitat de València, Colecciones de Criptógamas: VAL_Lich. 13 records from Seven new species of the genus Xestoleberis (Ostracoda: Podocopida: Cytheroidea) from the Fiji Archipelago. 1143 records from Palynological analysis of sediment core GeoB9508-5. 363 records from The cicadas (Hemiptera: Cicadidae) of India, Bangladesh, Bhutan, Myanmar, Nepal and Sri Lanka: an annotated provisional catalogue, regional checklist and bibliography. 9997 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3 records from Bryochoerus liupanensis sp. nov. and Pseudechiniscus chengi. sp. nov. (Tardigrada: Heterotardigrada: Echiniscidae) from China. 3 records from Three new species of Elachistidae (Lepidoptera: Gelechioidea) from India. 23 records from New data on the genus Domene (Coleoptera: Staphylinidae: Paederinae) of mainland China. 2215 records from Collection Polychaeta - ZSRO. 11 records from Specimens of Huffmanela lusitana of the Collection of Pathology of IPMA. 764 records from Centre d'Estudis Avançats de Blanes. Limnological Observatory of the Pyrenees - Fitoplancton de lagos pirenaicos. 21 records from Consolidated Checklist of Hard Corals of the Genus Acropora Oken, 1815 (Scleractinia: Acroporidae) in North Borneo, East Malaysia. 41 records from Revision of the genus Metaterpna Yazaki, 1992 (Lepidoptera, Geometridae, Geometrinae), with description of a new species from China. 1 records from A new species of Eumeces Wiegmann 1834 (Sauria: Scincidae) from Iran. 17 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 3 records from Mimogonellus dreybrodti sp. n., a new cave-inhabiting Osoriinae from Laos (Coleoptera: Staphylinidae). 9 records from Cleaning old cabinets: revealing the taxonomy of Sri Lankan wolf spiders (Araneae, Udubidae and Zoropsidae). 1851 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Pisces_Types. 42736 records from MSB Bird Collection (Arctos). 9038 records from Naturhistorisches Museum Mainz, Zoological Collection. 5 records from Coleophora meridiogallica Baldizzone, Huemer & Nel, sp. n. from France (Lepidoptera, Coleophoridae). 132 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 12 records from Zukünftiges NSG Höftland/Bockholmwik. 1 records from Arthropoden aus südostalpinen Höhlen.. 2 records from A new species of Isthmura (Caudata: Plethodontidae) from the montane cloud forest of central Veracruz, Mexico. 17 records from Three new species of Tridentella Richardson, 1905 (Isopoda: Cymothoida: Tridentellidae) from New Caledonia. 102944 records from Ichthyology Collection - Royal Ontario Museum. 25 records from Revision of African Apiocera (Diptera: Apioceridae). 4 records from A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China. 7 records from Two new species of Atopophlebia Flowers, 1980 (Ephemeroptera, Leptophlebiidae) from Colombia. 4051 records from Gunma Museum of Natural History, Fungi Specimen. 12 records from Aves de la expedición en lago de Tota, Boyacá - Proyecto Boyacá BIO. 2 records from Registro Herpetofauna de los Corregimientos de Juanchaco y Ladrilleros, Municipio de Buenaventura (Valle del Cauca) Septiembre de 2016. 35 records from Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae). 81 records from In the footsteps of history: the bees of the genus Hylaeus Fabricius (Hymenoptera, Apoidea: Colletidae) collected by V. I. Roborovsky and P. K. Kozlov in Northwest China (1895 - 1926). 2 records from A new species, new synonymy and new records of Mexican and Central American Xyleborini (Coleoptera: Curculionidae: Scolytinae). 22213 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 141 records from Macrohongos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 45 records from Excavating sponges from the Pacific of Central America, descriptions and a faunistic record. 5953 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 7204 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 50 records from A new genus and species of the family Symphysanodontidae, Cymatognathus aureolateralis (Actinopterygii: Perciformes) from Indonesia. 91253 records from CUMV Fish Collection. 36657 records from Plant Specimen from Herbarium (LBG) in China, Lushan Botanical Garden, Jiangxi and Chinese Academy of Sciences. 976457 records from EURISCO, The European Genetic Resources Search Catalogue. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 6922 records from MUST, Insecta. 57 records from Distribution of planktic foraminifera of sediment core GIK23400-3. 2116 records from Collection entomologique Pierre Lachiver. 3713631 records from The New York Botanical Garden Herbarium (NY). 50 records from Distribution of planktic foraminifera of sediment core PS1235-1 at stadium 5.5. 1485 records from Richard Staniforth Herbarium (UWPG). 50883 records from Naturalis Biodiversity Center (NL) - Paleobotany. 128961 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Plantae. 74258 records from Collection Arachnology SMF. 2 records from ZUEC-POP - Coleção de Polyplacophora do Museu de Zoologia da UNICAMP. 4 records from Amphicnemis valentini sp. nov. from the Cardamom ecoregion in Cambodia and Vietnam (Odonata: Coenagrionidae). 2 records from Discovery of a new millipede species in northern Vietnam, and the proposal of a new genus, Parariukiaria (Diplopoda, Polydesmida, Xystodesmidae). 144227 records from University of Michigan Museum of Zoology, Division of Mollusks. 686 records from Banco de información sobre características tecnológicas de maderas mexicanas. 4973 records from Data from CRSN herbarium digitization initiative under BID-funded project. 3 records from Mammalia (SMNH-MM). 2519 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 2860 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves (MFA-ZV-Or). 7 records from To the revision of the genus Thionia Stål (Hemiptera, Fulgoroidea, Issidae), with description of new genera and new subtribe. 2103 records from Flora ficológica de la huasteca potosina. 183585 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 2340 records from Type Specimen Database of Museum and Institute of Zoology PAS. 3784 records from Herbier de Wallis et Futuna. 6 records from A new species of Deltaspis Audinet-Serville (Coleoptera: Cerambycidae: Cerambycinae) from Mexico. 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 4 records from Three new species of Corynoneura Winnertz from Oriental China (Diptera: Chironomidae: Orthocladiinae). 2 records from A new species of the endemic Australian genus Hyptiogaster Kieffer (Hymenoptera: Gasteruptiidae). 1118 records from Herbario MAIA, colección Manuel Martín Bolaños. 24554 records from Akita Prefectural Museum, Insect Collection. 15464 records from Freshwater Diversity Identification for Europe (FREDIE) - funded by the German Leibniz association (
Keywords: GBIF; biodiversity; species occurrences